Synergistic enhancement of syngas production from vinegar residue via air-steam co-gasification: Performance and life cycle assessment - Feng Tan; Qi Wang; Ding Jiang; Pengyu Lu; Yixuan Zheng; Shuang Wang; Mao Mu; Anqing Zheng (Biomass and Bioenergy, 2027)

Mechanical and failure characteristics of a large-section shield tunnel incorporating a prefabricated bottom box culvert and secondary lining - Jialin Li; Kun Feng; Haixing Mu; Jiaqi Li; Wenqi Guo; Mingqing Xiao; Shaofeng Wang; Chuan He (Tunnelling and Underground Space Technology, 2026)

Integrated analysis reveals the effects of substituting pea with mung bean on microbial succession and metabolite profiles during medium-temperature Daqu fermentation - Ruijuan Wang; Lijun Yan; Feng Ding; Hao Zhou; Boyang Xu; Shanshan Xu; Yuhan Yuan; Dongdong Mu; Xuefeng Wu; Xingjiang Li (International Journal of Food Microbiology, 2026)

Mechanisms ofra Tetmethylpyrazine in spinal cord injury: a narrative review - Yu Jiang; Gang Liu; Huizhong Bai; Jiashu Yue; Bowen Deng; Feng Gao; Jinyu Li; Xiaohong Mu (Molecular Biology Reports, 2026)

Multiple magma sources and incremental assembly of the late Mesozoic Yunmengshan batholith, North China Craton: Constraints from zircon Hf-O isotopes and apatite geochemistry - Zi-Mu Li; Miao-Miao Ling-Hu; Shi Chen; Jin-Feng Sun; Ji-Heng Zhang; Ya-Dong Wu; Bao-Quan Zhou; Quan-Lin Hou; Jin-Hui Yang (Lithos, 2026)

Boron-mediated pectin demethylesterification improves Na+ retention in root cell wall and alleviates salt stress in Brassica napus L. - Yu Yang; Wenjing Hao; Rui Jing; Xiaolei Feng; Diqing Yin; Muhammad Riaz; Mu Lu; Yusheng Niu; Lei Yan (Plant Science, 2026)

Integrating scale-matched spatial scales into water scarcity risk screening in China - Jiayu Zhang; Dedi Liu; Jiabo Yin; Feng Yue; Jiaoyang Wang; Zhenyu Mu; Hanxu Liang; Zhilin Niu; Zhengbo Peng (Journal of Hydrology, 2026)

Static magnetic field coupled with magnetic biochar boosts methane production in sludge anaerobic digestion by activating dual electron transfer mechanisms - Likui Feng; Muzi Li; Kaiyi Zhang; Shuo Liu; Heng Liang; Zhelu Gao; Huizhi Mu; Shufei He; Qingliang Zhao; Liangliang Wei (Journal of Environmental Chemical Engineering, 2026)

Geochronology and Geochemistry of Cretaceous volcanic rocks in the Central Lhasa Block, China: Constraints on the evolution of the Neo-Tethys Ocean - Zhi-Qiang Kang; Rui Wang; Chun-Xi Shan; Ji-Feng Xu; Feng Yang; Sheng-Liang Pei; Ji-Zhong Mu; Ling-Ling Wu; Lu Zhou (Journal of Asian Earth Sciences, 2026)

Advances in MOF-enabled food preservation and packaging: A critical review of structure-function relationships, functionalization strategies, applications, and safety - Yinghua Tang; Yuqin Feng; Xuefeng Liu; Kuiran Liu; Wenhua Mu; Yating Song; Yuqing Duan; Guishan Liu (Food Research International, 2026)

Extraction optimization, purification, and structural characterization of Yacon polysaccharide: An inhibitor against α-glucosidase/α-amylase - Zhen-Zhou Li; Zhe-Xuan Mu; Shao-Feng Li; Yi-Han Ding; Shadrack Vundi Benjamin; Ruo-Jia Zhu; Xiang-Yu Wang; Zhen-Yu Wang; Hua Zhang (Food Chemistry, 2026)

Electrospun nanofiber interfaces for aquatic products preservation: spoilage microenvironments, molecular interactions, and mechanism-oriented design strategies - Kuiran Liu; Yuqin Feng; Xuefeng Liu; Yinghua Tang; Wenhua Mu; Yating Song; Yuqing Duan; Guishan Liu (Food Bioscience, 2026)

Upcycling hazardous electric arc furnace dust into defect-rich ZnO/ZnFe2O4 heterojunction for in situ H2O2 electrogeneration and water purification - Lijuan Jia; Bo Liu; Guoxing Mu; Yiqiang Ji; Fang Wang; Rui Cao; Ping Ning; Shuo Cui; Jiayu Feng (Chemical Engineering Journal, 2026)

Sulfuric acid-induced microphase separation strengthens poly(acrylic acid) hydrogels - Zheng Luo; Yuan Feng; Meng Mu; Xing Zhang; Heng Liu; Mingmin Zhang; Xin Su; Yujun Feng (Chemical Engineering Journal, 2026)

Integrated biological and chemical strategies for sustainable management of Nigrospora coryli-induced tobacco leaf spot - Jingpei Zou; Liuti Cai; Yiming Geng; Mengyu Yin; Yuguang Mu; Jingjing Guo; Hancheng Wang; Feng Zhang (Archives of Microbiology, 2026)

Analysis method for longitudinal structural response of shield tunnels incorporating iterative updates of circumferential joint bending and shear stiffness - Wenqi Guo; Kun Feng; Haixing Mu; Yili Zhou; Shaoyi Yang; Ruoyang Tang; Chuan He (Tunnelling and Underground Space Technology, 2026)

Study on the mechanism of selective flotation separation of fine coal and kaolinite enhanced by environmentally friendly small-molecule carboxylic acids - Wei Xiao; Yuping Fan; Xiaomin Ma; Jian Niu; Maoqing Yang; Xianshu Dong; Yuanpeng Fu; Zeyu Feng; Pengcheng Wen; Yanze Mu (Minerals Engineering, 2026)

Sustainable bio-aerogels for food packaging applications: Fabrication strategies, preservation mechanisms, and innovation trends - Xuefeng Liu; Yuqin Feng; Yating Song; Jiajun Guo; Kuiran Liu; Yinghua Tang; Wenhua Mu; Jianfang Li; Yuqing Duan; Guishan Liu (Food Research International, 2026)

In vitro screening and probiotic evaluation of lactic acid bacteria exhibiting potential to enhance intestinal barrier function and antioxidant properties - Shishen Liu; Lu Feng; Haijun Mu; Shenhuizi Chen; Xue Han; Qian Xu (Food Bioscience, 2026)

TME-activated MXene nanoheterojunctions engineer cancer cells through phototherapy and metabolic interference for enhanced cuproptosis and immunotherapy - Hui Li; Jie Geng; Min Mu; Susu Xiao; Chenqian Feng; Lihua Zhou; Yuanxiang Wang; Wei Yu; Rangrang Fan; Bo Han; Gang Guo (Chemical Engineering Journal, 2026)

Influence of inclination angle on the failure mechanisms and shear capacity of concave-convex tenon connections in shield tunnel joints - Haixing Mu; Kun Feng; Jialin Li; Jiaqi Li; Wenqi Guo; Yili Zhou; Lixiang Zhao; Chuan He (Tunnelling and Underground Space Technology, 2026)

Wave climate characteristics and long-term trends in the northern South China Sea: A 31-year hindcast study for offshore engineering applications - Jinzong Guan; Qianru Niu; Yanqing Feng; Yan Li; Xiaomei Liao; Lin Mu (Ocean Engineering, 2026)

Novel ex-situ functionalized bacterial cellulose-based packaging films with full hydrogen-bonded network for sustainable and bio-safety food preservation - Changqing Zhao; Lang Wu; Jiao Huang; Liguo Yin; Jiawei Wang; Zihao Feng; Lin Bai; Xingxiu Zhao; Zhifeng Zhao; Shengdong Mu (Food Research International, 2026)

Self-assembly-confined upconversion photogelation enables centimeter-deep curing for rapid deep-organ hemostasis with sustained pain modulation - Qian Chen; Hongyu Wen; Peng Zhang; Xuhui Xu; Hanying Wang; Guizhu Feng; Qiqi Pei; Li Tian; Yuanyuan Cao; Hongwei Qin; Fusheng Luo; Zhaowei Teng; et al. (Chemical Engineering Journal, 2026)

Artificial Intelligence for Atmospheric and Oceanic Forecasting and Research: A Fudan University Perspective - Guokun Dai; Hao Li; Mu Mu; Guihua Wang; Bo Qin; Xiaohui Zhong; Feng Zhang; X. San Liang (Advances in Atmospheric Sciences, 2026)

Inclusion of cyclic loading characteristics in a load–transfer analysis for jacket foundation piles in clay - Guangming Yu; Kewen Zhu; Hang Feng; Junlin Zhu; Linlong Mu (Marine Georesources & Geotechnology, 2026)

Effect of pile corner rounding on local scour around offshore wind turbine foundations in sands using CFD–DEM - Xiangyi Meng; Yifan Lu; Xiaoming Feng; Guizhong Tian; Yadong Zhu; Zhongqiu Mu (Computers and Geotechnics, 2026)

Amorphous nickel hydroxide accelerates interfacial water dissociation for efficient electrochemical nitrate decontamination and ammonia recovery - Xiaoyu Tian; Baixian Lu; Yanyu Zhang; Chaoran Shao; Ruiyan Fan; Jiachen Xie; Qingsong Mu; Yiwei Dai; Ziyan Feng; Qi Wang; Aimin Wang (Chemical Engineering Journal, 2026)

Tidal level seasonally modulates sediment organic carbon in seagrass meadows of tropical lagoon bays - Xiao-Ya Zhang; Hui-Jue Luo; Qian-Wei Li; Mu-Qiu Zhao; Zhen Ni; Yun-Feng Shi; Yin-Liu Wang; Yu-Chao Li (CATENA, 2026)

An ovarian follicle-based angiogenesis microphysiological system for high-efficiency screening of anti-angiogenic drugs - Xuebing Yang; Jing Liang; Nan Sun; Lu Mu; Jinfeng Xiong; Ge Wang; Kaiying Geng; Xie’an Feng; Yibo Wang; Shuo Zhang; Xueqiang Xu; Yan Zhang; et al. (Science Bulletin, 2026)

Acid-base imbalance electrolytic cell (AB-EC) for efficient treatment of acid mine drainage (AMD): Metal recovery and hydrogen production - Haoyang Song; Zhudi Chen; Jinyuan Jiang; Wei Tan; Zhaocong Ren; Mu Feng; Dongni Shi; Hongke Qin; Lei He; Xiaojun Pan; Kuk Cho (Journal of Environmental Chemical Engineering, 2026)

Innovations in arid land salinization management: Xinjiang's evolving paradigm for saline-alkali land governance - Jiandong Yu; Jihong Zhang; Zhenhua Wang; Li Guo; Jinzhu Zhang; Zhengjiang Feng; Yue Wen; Rui Chen; Xiaoguo Mu (Journal of Cleaner Production, 2026)

Hydrolysis of beef sarcoplasmic protein by dry-aged beef-isolated Yarrowia galli and its flavor characteristics - Siyu Guo; Zhiqi Liu; Yujia Liu; Tingyu Li; Jian Feng; Baide Mu; Hongmei Li; Juan Wang; Guanhao Li; Chunxiang Piao (International Journal of Gastronomy and Food Science, 2026)

K isotope behavior in topsoil from the southeastern margin of the Tibetan Plateau - Yanan Cheng; Jun Mu; Peizheng He; Cheng Cao; Shichao An; Can Zhang; Xiaoping Feng; Cheng Zhao; Xiao-Ming Liu (Geochimica et Cosmochimica Acta, 2026)

Pd nanoparticle-driven atomic hydrogen formation enhances electrocatalytic hydrodechlorination of florfenicol in wastewater - Haotian Mu; Chuanping Feng; Boaiqi Zhang; Nan Chen; Weiwu Hu (Chemical Engineering Journal, 2026)

Experimental investigation of contaminant dispersion in vertical drainage pipes induced by toilet flushing - Di Mu; Min Chang; Lu Feng; Ruibin Li; Yan Wu; Naiping Gao (Building and Environment, 2026)

Exposure to second-generation flame retardants and risk of metabolic diseases: a systematic review and meta-analysis - Li Shi; Wei Du; Xi-Yuan Peng; Juan Miao; Wei Li; Attiq Ur-Rehman; Meng-Wei Ge; Lu-Ting Shen; Rui Feng; Kang Zhong; Zhi-Ren Mu; Hong-Lin Chen (Archives of Toxicology, 2026)

Microbial Perspective: Regulatory Mechanisms of Interactions Between Microplastics and Dissolved Organic Matter on Greenhouse Gas Emissions in Aquatic Ecosystems - Mengxin Xu; Meiqi Huang; Shuang Liu; Jinze He; Feng Zhao; Bo Shao; Guangli Mu; Hongyang Cui; Panpan Cui; Yingxin Zhao; Yiwen Liu; Xiaoyu Cui; et al. (Global Change Biology, 2026)
Microplastic (MP) pollution may influence aquatic greenhouse gas (GHG) emissions by altering dissolved organic matter (DOM)–microbe coupling, yet reported effects remain inconsistent across ecosystems and exposure regimes. Here, we synthesized evidence from 16 studies to quantify the net effects of MPs on CO 2 , CH 4 , and N 2 O fluxes under ambient DOM conditions. Our meta‐analysis indicates that MP exposure significantly increases CO 2 emissions and decreases N 2 O fluxes, whereas CH 4 responses show a non‐significant positive trend with high variability. Exposure duration and polymer identity emerge as key moderators, indicating that MP effects are context‐dependent rather than uniform. Short‐term exposure tends to suppress carbon mineralization, whereas long‐term exposure is more often associated with GHG production, consistent with a time‐dependent trajectory potentially shaped by polymer aging. Mechanistically, this pattern may reflect initial DOM adsorption and humification that reduce substrate availability, followed by the release of bioavailable MP‐derived compounds that may stimulate microbial respiration, methanogenesis, and denitrification. Overall, MPs reshape aquatic carbon and nitrogen cycling within the overarching framework of DOM, which may ultimately influence GHG emissions under certain conditions. These findings provide a quantitative basis for reconciling conflicting observations and improving predictions of the climate relevance of MP pollution in aquatic ecosystems.

Two undescribed benzofuran derivatives from chaetomium elatum - Chen-Yi Yan; Feng Ju; Yu-Hui Chen; Yu-Ting Mu; Yun-Jie Hu; Da-Le Guo; Yun Deng; Qi-Xuan Kuang (Natural Product Research, 2026)

Real-time analysis of drillstring dynamic insertion and system vibration-induced wellbore wear in offshore directional well - Feng Tang; Yongsheng Liu; Lin Chai; Zongyang Mu; Xin Lei; Qiang Sun (Ocean Engineering, 2026)

A thermally induced solid–liquid phase transition strategy enhances pesticide efficacy by improving interfacial behavior - Haojie Gao; Zhongyi Li; Xiaochi Liu; Yujia Kang; Yunyu Tang; Jianfeng Tang; Wei Mu; Daxia Zhang; Xiangyang Li; Feng Liu (Chemical Engineering Journal, 2026)

Synergistic metabolism between Veillonella ratti and Lactobacillus acidophilus and its inhibition of enterohemorrhagic Escherichia coli infection in piglet - Wenhui Zheng; Yi Hao; Hejing Wang; Yuxin Han; Wenchao Song; Yanan Mu; Tianjia Feng; Zhaoyu Zhang; Bianfang Liu (Archives of Microbiology, 2026)

Biological control of a novel strain Bacillus velezensis BFWR11 against tomato early blight - Yuxin Han; Wenhui Zheng; Yanan Mu; Tianjia Feng; Yi Hao; Wenchao Song; Jin Cai; Boting Zhan; Zhaoyu Zhang; Bianfang Liu (Antonie van Leeuwenhoek, 2026)

The Potential Drug Target (Glycolysis Pathway) of the Spore Stage of the Pathogen Enterocytozoon hepatopenaei in Shrimp Farming - Bo Zhu; Juan Feng; Dong Qian; Ping Zhuang; Changkao Mu; Jiong Chen; Rongrong Ma (Fishes, 2026)
Enterocytozoon hepatopenaei (EHP) is a specialized parasitic microsporidian that causes significant economic losses to the shrimp farming industry. The glycolysis pathway plays an important role in the survival of EHP spores in vitro. In this study, key enzyme genes involved in the glycolysis pathway of EHP were analyzed, and purified spores were treated with KOH and a low temperature (−20 °C) to promote or inhibit germination. Quantitative analysis and enzyme activity of the initiating key gene hexokinase (HK) and the core link gene glyceraldehyde 3-phosphate dehydrogenase (GAPDH) were conducted to explore the energy response characteristics of germinating spores. The results showed that HK and GAPDH genes had significant differences from the host, based on phylogenetic analysis. The expression of HK gene and enzyme activity increased after promoting germination treatment. The expression of the GAPDH gene was stable, but the activity of the GAPDH enzyme increased significantly after germination promotion. These findings indicate that the inhibition of the HK gene expression level and GAPDH protein level can block spore germination and invasion in vitro, which could be used as potential control targets for EHP.

Effect of early-age loading, formwork removal time, and curing method on the cracking behavior of hydraulic lining concrete structures: Experimental analysis and multi-scale coupling cracking analysis model - Pengfei Li; Haoyu Wang; Xuehui An; Duoyin Wang; Ping Mu; Feng Sheng (Tunnelling and Underground Space Technology, 2026)

Enhanced radon concentration denoising in cemented coal gangue backfill: A novel hybrid VMD-SVD-SWT framework optimized by an improved SSSK-SCSO algorithm - Zekun Feng; Dongting Yang; Yong Chen; Wenping Mu (Journal of Environmental Radioactivity, 2026)

A novel antioxidant peptide DD12 (DWPDARGIWHND) derived from dry cured ham alleviates H2O2-induced oxidative damage via the Keap1-Nrf2-ARE pathway - Ying-dao Nan; Si-qi Chen; Guan-hao Li; Ting-yu Li; Bai-de Mu; Juan Wang; Jian Feng; Hong-mei Li; Chun-xiang Piao (Food Research International, 2026)

Numerical investigation of toilet flushing and exhaust fan operation on aerosol transmission dynamics in building drainage system - Di Mu; Min Chang; Lu Feng; Ruibin Li; Yan Wu; Naiping Gao (Building and Environment, 2026)

Integrative bulk and single-cell transcriptomic analyses reveal nucleus pulposus cell fibrosis as a therapeutic target in intervertebral disc degeneration and identify quercetin as a potential antifibrotic agent - Peilin He; Jun Tao; Guo Li; Ye Mu; Rong Hu; Junming Chen; Wenqi Feng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Dry and Wet Alternation Events in China during 1961–2020 - Hao Wu; Xuehua An; Yingxiao Sun; Dongdong Zuo; Jiayi Mu; Pengcheng Yan; Guolin Feng; Qianrong Ma (Journal of Meteorological Research, 2026)

Adaptations in ancient oasis woodlands of the hyper-arid Tarim Basin, Northwestern China: charcoal and coprolite analyses - Kangkang Li; Konglan Shao; Ying Yang; Gill Plunkett; Robert Spengler; Bing Xu; Yong Wu; Xiaohong Tian; Dong Wei; Chunxue Wang; Huiqiu Shao; Guijin Mu; et al. (Archaeological and Anthropological Sciences, 2026)

Design of robot navigation system under spatial constraints in shiitake mushroom fruiting room - Hualu Song; Kangkang Qi; Wenjie Feng; Yuanjie Mu; Jun Li; Xiangyu Lv; Zhichao Liang; Fengyun Wang (Computers and Electronics in Agriculture, 2026)

Numerical investigation on the errant vehicle–shield tunnel collision considering the XSD-incorporated anti-collision system - Ruoyang Tang; Kun Feng; Wenqi Guo; Delei Zou; Haixing Mu; Li Zhang; Chuan He (Tunnelling and Underground Space Technology, 2026)

Glacial melting enhances the influence of microbial cross-domain interactions on dissolved organic carbon dynamics across the high-altitude glacier-proglacial lake-river continuum - Yanan Zhou; Qing Yang; Hongyang Cui; Meiqi Huang; Zhao Xue; Guangli Mu; Feng Zhao; Liang Li; Xiaodong Li; Yindong Tong (Journal of Environmental Sciences, 2026)

High-value utilization of hazardous solid waste for efficient electrocatalytic oxygen reduction to produce hydrogen peroxide - Bo Liu; Xiaoshuang Song; Guoxin Mu; Jiayu Feng; Fang Wang; Rui Cao; Zibin Pan; Feixiang Lu; Ping Ning; Shuo Cui; Lijuan Jia (Environmental Research, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Sustainable synthesis of phosphate/silicate/biochar composites derived from oil shale semi-coke waste for efficient adsorption and passivation of heavy metals - Dandan Wang; Bin Mu; Feng Zhao; Yan Liu; Yongfeng Zhu; Aiqin Wang (Journal of Environmental Chemical Engineering, 2026)

Fe3O4 nanoparticles and cytochrome c synergistically facilitate lactate chain elongation to caproate - Yichao Wang; Chunhui Zhao; Fangyuan Feng; Yaomin Xi; Wenhan Chen; Xiaoyu Zhu; Xiang Li; Chuanshun Zhi; Hui Mu (Journal of Environmental Chemical Engineering, 2026)

Creating syngas and sulphur from H2S and CO2 over Mo-Cu based catalyst in a dielectric barrier discharge reactor - Lu Zhao; Wenshuang Feng; Xiaoliang Mu; Kegong Fang (Fuel, 2026)

Microbial succession–potential influence mechanism on flavor modulation in spontaneously fermented Moringa oleifera leaves: An integrative multi-omics approach - Yuhan Liu; Yuwei Guo; Hongyu Mu; Muhammad Aaqil; Feng Zhang; Jingchuan Zheng; Jun Sheng; Yang Tian; Cunchao Zhao (Food Research International, 2026)

Recent advances in cellulose-based paper for flexible pressure sensors: A review - Qinghua Liu; Leihuan Mu; Jiehui Li; Jinmei He; Hui Liu; Menglin Zhu; Pu Feng; Xuedan Zhu; Cai-Li Sun; Mengnan Qu (Carbohydrate Polymers, 2026)

FM-SAM: individual tree crown delineation and classification based on Segmentation Anything Model (SAM) and YOLOv10 in UAV imagery for forest monitoring - Haohua Que; Haojia Gao; Weihao Shan; Mingkai Liu; Jianshuo An; Fei Deng; Shuo Feng; Xinghua Yang; Lei Mu (Computers and Electronics in Agriculture, 2026)

A lightweight detection algorithm for cereal weed recognition based on deep learning - Xiao-Wei Dong; Lin-Feng Wang; Xi-Mu Zhang; Ming Wang; Wei-Kai Li (Crop Protection, 2026)

Dual mutations containing E198A in β-tubulin eliminate the negative cross-resistance between carbendazim and diethofencarb in Corynespora cassiicola - Jingkun Han; Jiamei Zhu; Jin Li; Dicheng Ma; Wei Mu; Hongqiang Dong; Feng Liu (Pesticide Biochemistry and Physiology, 2026)

Observation of out-of-plane ferroelectricity in ∼5 nm ultrathin SrBi2Ta2O9 films for memristors and synapses application - Li-Ping Tan; Xue-Feng Hu; A-Long Li; Wei-Wei Qing; Ming Zhou; De-Bao Yu; Guo-Peng Zhang; Qing-Qing Mu; Zi-Long Wang; Xiao-Liang Wang; Ya-Li Bi; Wei Zhang (Chemical Engineering Journal, 2026)

Mechanistic insights into sulfidated nanoscale zero-valent iron enhanced methanogenesis: Electron redistribution and direct interspecies electron transfer-driven metabolic reconfiguration - Fangyuan Feng; Chunhui Zhao; Yinguang Chen; Yongfang Zhang; Xiaonong Hu; Hui Mu; Wen Zhang (Bioresource Technology, 2026)

Physics-informed neural network for hydraulic prediction in open-channel water transfer projects with sparse monitoring data - Zhongbin Li; Tong Mu; Xin Li; Pengcheng Li; Jiangang Feng; Hui Xu; Chunsheng Liu; Shangtuo Qian (Water Research, 2025)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Aerodynamic performance degradation of offshore wind turbine blades under icing with varying angles of attack - Zhongqiu Mu; Guizhong Tian; Xiaoming Feng; Senlin Mu; Fanting Kong; Bin Zhang; Xiangyi Meng (Ocean Engineering, 2025)

Persistent high methane production and CO2 reduction by multiple coal biodegradation under the application of electric field - Xiao Feng; Jiayan Zhang; Hongguang Guo; Xiaogang Mu (Journal of Cleaner Production, 2025)

Development of a magnetite-oyster shell composite to improve methanogenesis in carbohydrate-rich wastewater treatment - Fangyuan Feng; Yichao Wang; Jingyang Luo; Chunhui Zhao; Yongfang Zhang; Chuanshun Zhi; Hui Mu (Journal of Environmental Chemical Engineering, 2025)

From mung bean to Minglv-flavor baijiu: Unraveling the signature aroma profile and aging dynamic - Ruijuan Wang; Lijun Yan; Feng Ding; Shanshan Xu; Weiqi Hu; Ling Zhang; Boyang Xu; Hao Zhou; Dongdong Mu; Xingjiang Li (Food Chemistry, 2025)

Correction: Fine mapping of the dominant female sterility gene and novel model of hybrid seed production in cabbage (Brassica oleracea L. var. capitata) - Wenjing Ren; Jinchao Si; Jiamin Li; Yiliao Feng; Yuankang Wu; Xinyu Zhao; Chunyu Jiang; Limei Yang; Mu Zhuang; Honghao Lv; Yong Wang; Jialei Ji; et al. (Theoretical and Applied Genetics, 2025)

Golgi-associated TRAF6 as a regulator of protein convertase FURIN for insulin receptor precursor processing - Minjun Liu; Kun Zhou; Yang Sheng; Wen Zhang; Qiaoli Chen; Ziyue Chen; Xinyu Yang; Yuxin Jin; Fangtong Liu; Yinqiu Mu; Shu Su; Weikuan Feng; et al. (Science China Life Sciences, 2025)

Predicting internal carotid artery system risk based on common carotid artery by machine learning - Yuhao Tong; Qingyi Zhang; Feng Zhang; Weidong Mu; Steven W. Su; Lin Liu (Medical & Biological Engineering & Computing, 2025)

MASS-LSVD: A Large-Scale First-View Dataset for Marine Vessel Detection - Yunsheng Fan; Dongjie Ju; Bing Han; Feng Sun; Liran Shen; Zongjiang Gao; Dongdong Mu; Longhui Niu (Journal of Marine Science and Engineering, 2025)
In this paper, we release a new large-scale dataset containing multiple categories of ships and floating objects at sea, which we call MASS-LSVD. It is used to train and validate target detection algorithms and future large models for ship autopiloting. The dataset was captured by a visible light camera installed aboard the world’s first intelligent research, teaching, and training ship, “Xinhongzhuan”. This MASS (maritime autonomous surface ship) was operated by Dalian Maritime University, China. We have collected more than 4000 h of video of the “Xinhongzhuan” vessel’s voyage in the Bohai Sea and other areas, which are carefully classified and filtered to cover as much as possible the various types of sample data in the marine environment, such as light intensity, weather, hull shading, data from ocean-going voyages, entering and exiting ports, etc. The dataset contains 64,263 1K-resolution images captured from video footage, covering four main ship types: Fishing Boat, Bulk Carrier, Cruise Ship, Container ship, and an ‘Other Ships’ class, for vessels that cannot be specifically classified. The dataset currently contains 64,263 pairs of 1K-resolution images covering four common ship types (fishing boat, bulk carrier, cruise ship, container, and other ship, where no specific ship type can be determined). All the images have been labeled with high-precision manual bounding boxes. In this paper, the MASS-LSVD dataset is used as the basis for training various target detection algorithms and comparing them with other datasets, which compensates for the lack of first-view images in the vessel target detection dataset, and MASS-LSVD is expected to be used to facilitate the research and application of autonomous ship navigation models in the framework of computer vision.

Global Fixed-Time Target Enclosing Tracking Control for an Unmanned Surface Vehicle Under Unknown Velocity States and Actuator Saturation - Xinjie Han; Guanglu Ma; Yunsheng Fan; Dongdong Mu; Feng Sun; Linlong Shi; Hongbiao Li (Journal of Marine Science and Engineering, 2025)
This paper presents a global fixed-time control framework to address the target circumnavigation tracking problem of underactuated unmanned surface vehicles (USV) under unknown velocity states, lumped uncertainties, and actuator saturation. At the core of this approach is a novel fixed-time target-enclosing line-of-sight (FTTELOS) guidance law, designed to generate the desired heading angle and surge velocity. To estimate unknown velocities, external disturbances, and unmeasured system states, a set of fixed-time observers is constructed, consisting of a velocity observer, a disturbance observer, and a high-dimensional extended state observer (HFTESO). Moreover, to enhance robustness and effectively tackle actuator saturation, the control scheme incorporates a fixed-time sliding mode controller, a dynamic auxiliary system, and a fixed-threshold event-triggered mechanism. Simulation results using SimuNPS demonstrate that the proposed method enables rapid and smooth target circumnavigation, with all system errors converging to an arbitrarily small neighborhood of the origin within a fixed time. Theoretical analysis and simulation studies confirm the effectiveness and robustness of both the FTTELOS guidance law and the integrated control strategy. Quantitatively, compared with the traditional target-enclosing line-of-sight (TELOS) method, the proposed FTTELOS reduces the convergence time of the distance error δe from 13.64 s to 10.22 s and the angular error ϕe from 10.46 s to 7.52 s, demonstrating a significant improvement in convergence speed and overall control performance.

Enhancing granular sludge stability: Insights from the superior performance of biofilms - Xin Wang; Xiaoran Feng; Zhibang Mu; Mingshan Wang; Chengjian Yang; Guohui Lv; Zhihua Li (Journal of Water Process Engineering, 2025)

Synergistic effects of nutrient competition, biotic interactions, and hydrological regulation drive green tide outbreaks in the South Yellow Sea - Guanbing Feng; Jingfei Liu; Ning Wang; Lihua Xia; Jiahao Fan; Qingqing Mu; Yuqing Sun; Peiming He; Jianheng Zhang (Harmful Algae, 2025)

Integration LC-MS/MS and molecular modeling techniques to elucidate the molecular mechanisms of goat whey protein-IgG interactions - Hongbo Li; Quan Gao; Xianjun Gao; Geng Long; Meng Bian; Shuo Feng; Shanbo Mu; Hongjuan Li; Jinghua Yu (Food Chemistry, 2025)

Emissions and carbon isotopic signatures of polycyclic aromatic compounds (PAHs, OPAHs) produced by coking in China - Jiajie Li; Ling Mu; Xiaofan Li; Xiaofeng Liu; Huiling Bai; Chuanyang Feng; Xin Jiang; Ying Wei; Chenhui Li (Environmental Pollution, 2025)

Synergistic Co single-atom/nanoparticle catalysis enables stable hydrogenation of levulinic acid to gamma-valerolactone with formic acid - He Huang; Wei Zhang; Jianrong Zeng; Mengke Liu; Han Lin; Liwen Mu; Xin Feng; Xiaohua Lu; Lilong Zhang; Jiahua Zhu (Chemical Engineering Journal, 2025)

Investigation on the force transmission performance between segmental rings of super-large cross-section shield tunnels - Wenqi Guo; Kun Feng; Haixing Mu; Jiaqi Li; Yili Zhou; Chuan He (Tunnelling and Underground Space Technology, 2025)

Oyster shell immobilized nano zero-valent iron for enhancing methane production from carbohydrate-rich food waste: Characterization, performance, and mechanism - Xiaofan Ding; Wei Jiang; Fangyuan Feng; Bochang Feng; Yanfei Li; Yongfang Zhang; Chuanshun Zhi; Chunhui Zhao; Jingyang Luo; Hui Mu (Journal of Environmental Chemical Engineering, 2025)

Emission fluxes of nitrous acid (HONO) from livestock and poultry wastes - Wenjin Zhang; Pengfei Liu; Min Song; Xuran Li; Xiaoxi Zhao; Yifei Song; Di Tian; Chenglong Zhang; Yuanyuan Zhang; Yangang Ren; Chengtang Liu; Junfeng Liu; et al. (Journal of Environmental Sciences, 2025)

Interface modification of fluopyram-loaded microcapsules using Fe3+/lignosulfonate via coordination and electrostatic interactions to improve nematicide rhizosphere utilization - Haichao Cao; Yanhou Zhao; Jiangzhou Li; Kuai Dai; Lijun Jiang; Wenzheng Ling; Wei Mu; Chao Feng; Dan Chen; Jinguang Yang (Chemical Engineering Journal, 2025)

Fine mapping of the dominant female sterility gene and novel model of hybrid seed production in cabbage (Brassica oleracea L. var. capitata) - Wenjing Ren; Jinchao Si; Jiamin Li; Yiliao Feng; Yuankang Wu; Xinyu Zhao; Chunyu Jiang; Limei Yang; Mu Zhuang; Honghao Lv; Yong Wang; Jialei Ji; et al. (Theoretical and Applied Genetics, 2025)

HMGA2 Attenuates Tendon Stem/Progenitor Cell Senescence Via PI3K/AKT-Mediated Mitophagy Activation and SASP Suppression - Hao Wang; Guang-Chun Dai; Yu-Cheng Gao; Xiao-Yu Liu; Pan-Pan Lu; Mu-Min Cao; Ren-Wang Sheng; Liu Shi; Zhang Cheng; Ying-Juan Li; Yun-Feng Rui (Stem Cell Reviews and Reports, 2025)

Alternative splicing of OsNPR3 promoted by the bacterial TAL effectors-targeted splicing regulator OsRBP11 antagonizes OsNPR1 function and enhances disease susceptibility in rice - Xiaochen Chen; Xiaohui Yao; Fang Yan; Shaofang Li; Zuo-Dong Wang; Fu-You Yin; Miao Zhou; Zhen Wang; Lina Qin; Baoguo Zhao; Kai Lu; Liyuan Zhang; et al. (Molecular Plant, 2025)

Effects of metal oxides loaded with biochar on adsorption of cationic and anionic metals: A meta-analysis - Yang Yu; Xinwei Chen; Lingxin Zhao; Shufei He; Likui Feng; Weixin Zhao; Huizhi Mu; Qingliang Zhao; Liangliang Wei (Journal of Environmental Management, 2025)

Enhanced biodegradation of crude oil by phosphate-solubilizing bacteria Bacillus subtilis PSB-1: Overcoming soluble phosphorus deficiency - Xudong Wang; Zhuorong Du; Zhenzhen Li; Mei Liu; Jun Mu; Lijuan Feng; Zhi Chen; Qingguo Chen (Journal of Environmental Management, 2025)

From error ellipse to Bayesian estimation: Strategies for optimizing T-W diagrams in UPb dating - Yao Mu; Can Ge; Fangyue Wang; Xiuyu Li; He Sun; Haiou Gu; Feng Yuan (Geochemistry, 2025)

Functional expression of proton pumps in Rhodobacter sphaeroides enhanced energy supply and photo-fermentative hydrogen production - Xuefang Mu; Yuntong Xu; Yu Ma; Zixuan Gao; Jiali Feng; Minmin Wang; Wen Cao; Liejin Guo (Bioresource Technology, 2025)

Fluorine-induced dynamic surface reconstruction and interface modulation of NiMoO4 nanowire for enhanced urea degradation - Yunlong Bai; Jianguo Li; Lulu Wang; Jianjia Mu; Zhongbao Feng (Chemical Engineering Journal, 2025)

BRCA-CN: a blockchain-based framework to support public variant databases sharing in multi-center community for diagnostic reference and China regulatory science - Shoufang Qu; Rongzhi Liu; Shisen Li; Chuanfeng Huang; Yingqian Zhang; Xuan Gao; Pingping Dai; Chao Xu; Rutao Yang; Xuchao Li; Guojun Ouyang; Kang Shao; et al. (Human Genetics, 2025)

A new phenolic compound from Persicaria capitata - Lei He; Fei Zhong; Xing-Jun Chen; Ya-Ru Yang; Xue-Long Yan; Ming-Hui He; Xu Zhang; Mu-Zhen Wang; Yong-Qin Zeng; Qin-Feng Zhu; Zhu Zeng; Bo Tu; et al. (Natural Product Research, 2025)

Behavioral, Hematological, Histological, Physiological Regulation and Gene Expression in Response to Heat Stress in Amur Minnow (Phoxinus lagowskii) - Weijie Mu; Jing Wang; Yanyan Zhou; Shibo Feng; Ye Huang; Qianyu Li (Fishes, 2025)
Rising water temperatures due to climate change pose a significant threat to Phoxinus lagowskii, a cold-water fish that is ecologically vital to the high-latitude regions of China. This study assessed heat stress effects on behavioral, hematological, histological, physiological, and molecular responses in P. lagowskii. The critical maximum temperature (CTmax) was determined using the loss of equilibrium (LOE) method, with the CTmax reaching 29 °C. Elevated temperatures lead to an increase in the OBR. Fish were subjected to acute heat stress at 28 °C (below CTmax) for 48 h, with samples collected during the 48 h period. RBC, WBC, HGB, and HCT significantly increased during heat stress but decreased 12 h after heat stress. The levels of serum cortisol and blood glucose after heat stress were significantly higher than those in the control group. After heat stress, the height of the ILCM in the gills increased significantly, and the liver exhibited vacuolar degeneration and hypopigmentation. The activities of Na+-K+-ATPase and Ca2+-Mg2+-ATPase in the gills initially increased and then decreased over the duration of heat stress. Most enzyme activities (PK, LDH, PFK, and HK) decreased during heat stress, while LPL and HL levels increased, indicating that lipid metabolism was the primary utilization process under heat stress. There was an increase in SOD activity at 12 h, followed by a decrease at 24 h, and an increase in CAT activity under heat stress. Integrated biomarker response (IBR) and principal component analysis (PCA) were employed to synthesize multi-level responses. The IBR values reached their peak at 3 h and 48 h of heat stress. We observed an upregulation of heat shock proteins (Hsp70, Hsp90, and Hsc70) as well as interleukin-10 (IL-10) in response to heat stress. Our findings offer novel insights into the mechanisms underlying the heat stress response in P. lagowskii, thereby enhancing our understanding of the effects of heat stress on cold-water fish.

Understanding phytotoxicity of fosthiazate on crop seedlings through uptake kinetics, ROS burst and chloroplast metabolism - Jiamei Zhu; Min Jiang; Wen Sun; Xiaochi Liu; Wenjian Dou; Yujie Gao; Tao Zhang; Jianfeng Tang; Wei Mu; Nan Zou; Feng Liu (Journal of Hazardous Materials, 2025)

Corrigendum to “Changes of unique flavor substances and metabolic pathway brought by Lacticaseibacillus rhamnosus WH. FH-19 fermented milk during fermentation and storage stage: HS-SPME-GC-MS and HPLC-MS-based analysis” [Food Bioscience 65 (2025) 1–11/105974] - Lu Feng; Jingxia Yang; Liping Sun; Xiaoyan Zhu; Wei Lan; Guangqing Mu; Xuemei Zhu (Food Bioscience, 2025)

Potential Impacts of the North Atlantic Horseshoe Pattern on China Compound Heat‐Humidity Extremes - Jiayi Mu; Qianrong Ma; Shiquan Wan; Rui Hu; Shujuan Hu; Guolin Feng (International Journal of Climatology, 2025)
Compound heat‐humidity extremes (CHHEs) have gained significant attention as crucial indicators of heat stress. This research investigates the summer wet bulb globe temperature (WBGT) to elucidate the spatial variation of CHHEs across China from 1961 to 2022. The results reveal a clear increase in CHHEs, with the highest WBGT observed in southeastern China, while significant increases are noted in the northwestern and northeastern regions. Empirical orthogonal function analysis identifies three leading patterns: a consistent spatial increase, a north (decreasing)–south (increasing) dipole, and a west (decreasing)–east (increasing) dipole. Both observations and model simulations indicate that the North Atlantic Horseshoe (NAH) sea surface temperature (SST) anomaly pattern is a reliable predictor for CHHEs in China via influencing the North Atlantic Oscillation (NAO) and modulating large‐scale circulations. This combined with the westward extension of the Western North Pacific Anomalous Anticyclone (WNPAC), leads to a consistent rise in CHHEs, particularly in Central China. Regarding the north–south dipole, air‐sea interactions driven by the NAH reinforce the negative phase of the Eurasian (EU) teleconnection pattern through the NAO, intensifying cyclonic and anticyclonic anomalies over Mongolia to northern China and southern China, respectively. Furthermore, the NAH pattern during May–July effectively predicts summer CHHEs north–south dipole variations using the genetic algorithm‐based evolving neural network. This research offers valuable insights for predicting CHHEs in China from the perspective of North Atlantic SST anomalies.

DEM-DDM study on the humidification uniformity of brown rice in a pan coater - Xiangyi Meng; Yadong Zhu; Zhongqiu Mu; Guizhong Tian; Xiaoming Feng; Bin Zhang; Yongsheng Pei; Yifan Lu (Biosystems Engineering, 2025)

Targeting IGF1 to alleviate obesity through regulating energy expenditure and fat deposition - Ping Rong; Yinqiu Mu; Meiqin Wang; Liang Chen; Fangtong Liu; Yuxin Jin; Weikuan Feng; Kun Zhou; Hui Liang; Hong-Yu Wang; Shuai Chen (Science China Life Sciences, 2025)

Activation of NR2A-Wnt-TLR2 Signaling Axis in Satellite Glial Cells of the Dorsal Root Ganglion Contributes to Neuropathic Pain Induced by Nerve Injury in Diabetic Mice - Yan-Yan Zhang; De-Xin Zhu; Mu-Yun Wang; Ya-Ting Yi; Yu-Heng Feng; Cheng Zhou; Chun-Jie Li; Fei Liu; Jie-Fei Shen (Molecular Neurobiology, 2025)

Investigation of brittle characteristics and hydraulic fracture propagation in deep sandstone reservoirs in the central Junggar Basin - Lianchong Li; Jian Lu; Wenqiang Mu; Ran Ding; Anhai Zhong; Feng Yang; Mingyang Zhai (Bulletin of Engineering Geology and the Environment, 2025)

A Review on Development, Challenges, and Future Perspectives of Ensemble Forecast - Jing Chen; Yuejian Zhu; Wansuo Duan; Xiefei Zhi; Jinzhong Min; Xiaoli Li; Guo Deng; Huiling Yuan; Jie Feng; Jun Du; Qiaoping Li; Jiandong Gong; et al. (Journal of Meteorological Research, 2025)

Construction of the dynamic measurement algorithm for well inclination and azimuth in strapdown stable platform - Feng Sun; Rui Zhang; Yi-feng Wang; Wei Chen; Hui-dong Mu; Rui-wen Feng (Applied Geophysics, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Rational application of QoIs fungicides to achieve a rice-fungi-fish interaction balance within paddy ecosystems - Hong Li; Xueqing Wang; Beixing Li; Jin Lin; Feng Liu; Wei Mu (Environmental Pollution, 2025)

Polymer-derived C-Sn/SnO2@rGO heterostructures with dual assistance of gallic acid for high-performance lithium-ion batteries - Guanwen Wang; Baoyi Mu; Ke Cao; Chunlei Chi; Chuanqing Wang; Chao Huangfu; Fan Feng; Bin Qi; Qiushi Miao; Xinhou Yang; Zheng Liu; Tong Wei; et al. (Chemical Engineering Journal, 2025)

High-entropy (FeMnMoNi)Se2 nanoflower structure with multi-active sites for urea-assisted hydrogen generation - Yumo Fu; Hao Liu; Bo Gao; Jianjia Mu; Guoqing Guan; Zhongbao Feng (Chemical Engineering Journal, 2025)

Smart temperature sensors based on flexible CB/TPU/ PVDF membranes for eliminating pressure interference - Shuo Li; Jiaxin Sun; Feng Tong; Guo Chen; Zhefu Mu; Xiaoqiang Zhang; Sheng Huang; Zheng Chen; Lei Xu; Changyun Li; Peng Wang; Xiuquan Gu (Chemical Engineering Journal, 2025)

Occurrence, source, and microbial-driven fate of aliphatic and polycyclic aromatic hydrocarbons in sediments in the Magellan seamount region - Lingbo Jiang; Feng Zeng; Guoquan Wang; Zhaochao Deng; Hanghai Zhou; Chunlei Chen; Qinglin Mu; Kuiyong Bu; Shaoxiong Zhou; Chunfang Zhang; Yifei Dai (Marine Pollution Bulletin, 2025)

Targeted mutagenesis and functional marker development of two Bna.TAC1s conferring novel rapeseed germplasm with compact architecture - Bin Feng; Yu Wang; Xiaolong Zhang; Tingting Mu; Biaoming Zhang; Yan Li; Haitao Zhang; Wei Hua; Wenya Yuan; Haitao Li (Theoretical and Applied Genetics, 2025)

Hypogene sulfide precipitation during phyllic alteration: insights from copper isotopic evolution of the Dexing porphyry Cu–Mo–Au deposit, South China - Jia-Feng He; Guo-Guang Wang; Matthew J. Brzozowski; Pei Ni; Xiang-Long Luo; Jun Mu; Weiqiang Li (Mineralium Deposita, 2025)

Changes of unique flavor substances and metabolic pathway brought by Lacticaseibacillus rhamnosus WH. FH-19 fermented milk during fermentation and storage stage: HS-SPME-GC-MS and HPLC-MS-based analysis - Lu Feng; Jingxia Yang; Liping Sun; Xiaoyan Zhu; Wei Lan; Guangqing Mu; Xuemei Zhu (Food Bioscience, 2025)

Self-gelated flexible lignin-based ionohydrogels for efficient self-powered strain sensors - Jiahui Mu; Cuihuan Li; Deqiang Li; Xianliang Song; Sheng Chen; Feng Xu (Chemical Engineering Journal, 2025)

Associations between co-exposure to multiple heavy metals and age-related macular degeneration: A cross-sectional study - Mu-hong Wei; Ju-xiao Li; Jing Mi; Qing Wang; Feng Xu; Che Xu (Journal of Trace Elements in Medicine and Biology, 2025)

Oxygen vacancies enhanced peroxymonosulfate activation by accelerating electron shuttle over carbon-hybrid defective Mn2O3: Mechanistic insight into the singlet oxygen dominated pathway - Yang Xiao; Jincheng Mu; Qiong Peng; Jinming Feng; Bihui Zhou; Nannan Zhang; Baojun Liu (Journal of Environmental Chemical Engineering, 2025)

Upcycling acid waste gas containing H2S and CO2 into syngas and sulfur by non-thermal plasma coupled with Zn-Mo/Al2O3 catalyst - Wenshuang Feng; Xiaomeng Yuwen; Xiaoliang Mu; Lu Zhao; Kegong Fang (Fuel, 2025)

Highly selective capture of Ni2+ from complex environments by a sandwich-like layered metal sulfide ion exchanger - Mingdong Zhang; Qisheng Hong; Yuan Aocheng; Yan Zhang; Xiaoying Huang; Meiling Feng; Jingli Mu (Journal of Hazardous Materials, 2025)

Lignite degraded by Trichoderma citrinoviride: Products, processes and mechanisms - Xingyu Mu; Meitong Li; Jianhua Tian; Wenjiao Yuan; Hui Shen; Ruijie Zhang; Shuwei Li; Xin Feng; Xuening Fei; Yuhong Xie (International Biodeterioration & Biodegradation, 2025)

Mercury isotope evidence for Middle Ordovician photic-zone euxinia: Implications for termination of the Great Ordovician biodiversification event - Mu Liu; Wei Yuan; Chaogang Fang; Xun Wang; Ning Tan; Mingyu Zhao; Xiangli Wang; Thomas J. Algeo; Peng Sun; Xinbin Feng; Daizhao Chen (Gondwana Research, 2025)

High-performance biomass moisture-electric generators derived from Distillers’ spent grains: Synthesis, photothermal enhancement, and environmental sensing applications - Haichuan Gao; Zihao Feng; Wenjun Li; Jiatian Zhu; Shengdong Mu; Hongkai Zhang; Genqiao Liu; Wei Zhao; Bailiang Xue; Yonghao Ni (Chemical Engineering Journal, 2025)

Construction of Al-doped FeCoP nanosheet array with superhydrophilic/superaerophobic characteristics as a bifunctional electrocatalyst for activating alkaline overall water splitting - Jinmei He; Yuqing Wang; Leihuan Mu; Jiehui Li; Yurou Dong; Ying Zhang; Yuan Deng; Pu Feng; Mengnan Qu (Journal of Water Process Engineering, 2024)

Activation of microbial community and enhancement of quality by inoculating Zygosaccharomyces rouxii during the post-fermentation stage of Doubanjiang - Danyu Yan; Qi Qi; Linpei Liu; Lei Feng; Peiyi Deng; Zhuo Chen; Yingchun Mu; Wei Su (Food Research International, 2024)

Cellulose-based colorimetric/ratiometric fluorescence sensor for visual detecting amines and anti-counterfeiting - Cuihuan Li; Yuan He; Jiankang Zhang; Jiahui Mu; Junya Wang; Mengyao Cao; Haq Nawaz; Sheng Chen; Feng Xu (Carbohydrate Polymers, 2024)

Risk assessment of cough droplets in both static and dynamic indoor environments with different ventilation strategies - Kaijun Li; Ruibin Li; Lingjun Xiao; Lu Feng; Di Mu; Xing Shi; Naiping Gao (Building and Environment, 2024)

Microbial transformation of lignite into methane: Insights from anaerobic-activated sludge systems - Ruijie Zhang; Meitong Li; Wenjiao Yuan; Xin Feng; Xuening Fei; Xingcheng Zhao; Gangzhen Jiao; Hui Shen; Xingyu Mu; Yuhong Xie (Bioresource Technology Reports, 2024)

β-arrestin2 promotes angiogenesis of liver sinusoidal endothelial cells through the VEGF/VEGFR2 pathway to aggravate cirrhosis - Feng Gao; Wei Mu; Jiangbo Fan; Jing Shen (Toxicology Letters, 2024)

NHX5/NHX6/SPY22 complex regulates BRI1 and brassinosteroid signaling in Arabidopsis - Jun Shang; Guoxiu Mu; Yuting Qi; Xiao Zhang; Wei Shen; Yujie Xie; Mingrui Ge; Yu He; Feng Qiao; Quan-Sheng Qiu (Journal of Plant Physiology, 2024)

From flavor to function: A review of fermented fruit drinks, their microbial profiles and health benefits - Yu-Han Yuan; Dong-Dong Mu; Li Guo; Xue-Feng Wu; Xiang-Song Chen; Xing-Jiang Li (Food Research International, 2024)

Segmentation of Chinese consumer preference for wine extrinsic attributes based on stratification and weighted clustering algorithm - Yumeng Feng; Xiaoqian Wu; Weisong Mu; Mengyang Fan; Jianying Feng (Food Research International, 2024)

Functional characterization of large yellow croaker (Larimichthys crocea) Peroxiredoxin IV (PrxIV) gene promoter - Xianhui Wang; Pengfei Mu; Jieying Huo; Feng Han; Xinhua Chen; Jingqun Ao (Fish & Shellfish Immunology, 2024)

A synergetic binary system of waste cooking oil-derived bio-based surfactants and its interfacial performance for enhanced oil recovery - Ming-Yue Liang; Chi Ma; Wan-Qi Qin; Homely Isaya Mtui; Wei Wang; Jin-feng Liu; Shi-Zhong Yang; Bo-Zhong Mu (Colloids and Surfaces C: Environmental Aspects, 2024)

Generation and emission mechanism of polycyclic aromatic hydrocarbon (PAHs) during the coking process in Shanxi, China - Ziye Liu; Ling Mu; Chuanyang Feng; Xiaofan Li; Tian Liu; Xin Jiang; Huiling Bai; Xiaofeng Liu (Science of The Total Environment, 2024)

Use of Tirofiban to Prevent Ischemic Events in Patients with CYP2C19 Loss-of-Function Alleles during Flow Diversion of Intracranial Aneurysm: A Multicenter Cohort Study - Yangyang Zhou; Huibin Kang; Wenqiang Li; Bin Luo; Chao Wang; Ruhang Xie; Yongnan Zhu; Qichen Peng; Yisen Zhang; Jian Liu; Ying Zhang; Shiqing Mu; et al. (Translational Stroke Research, 2024)

Ferroptosis and Pyroptosis in Epilepsy - Fan Feng; Rong Luo; Dezhi Mu; Qianyun Cai (Molecular Neurobiology, 2024)

Asymmetric impact of ENSO on the late winter Warm Arctic-Cold Eurasian pattern - Gaoyuan Mu; Wenjun Zhang; Feng Jiang; Dingzhu Hu; Fei-Fei Jin (Climate Dynamics, 2024)

Exploring the viability of peracetic acid-mediated antibiotic degradation in wastewater through activation with electrogenerated HClO - Wang Lu; Nan Chen; Chuanping Feng; Ignasi Sirés; Ning An; Haotian Mu (Water Research, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Genome-wide analysis of TOPLESS/TOPLESS-RELATED co-repressors and functional characterization of BnaA9.TPL regulating the embryogenesis and leaf morphology in rapeseed - Xiaolong Zhang; Yingying Chen; Hongyu Chen; Chaocheng Guo; Xue Su; Tingting Mu; Bin Feng; Yu Wang; Zhixin Liu; Biaoming Zhang; Yan Li; Haitao Zhang; et al. (Plant Science, 2024)

Revealing the comprehensive effect of mechanization on sauce-flavor Daqu through high-throughput sequencing and multi-dimensional metabolite profiling - Yu Mu; Ying Huang; Dong Li; Zhiyu Zhu; Shirui Yu; Feng Xie (Food Research International, 2024)

Constructing efficient lithium salt dissociation solid-state electrolytes with high conductivity and transference number of Li ions for stable all-solid-state lithium batteries - Zengcai Guo; Shimin Liao; Feng Li; Linlin Shi; Bihai Su; Jingbo Mu; Yanming Wang; Zhongkai Huang; Feng Xu; Chaowen Guan (Chemical Engineering Journal, 2024)

A zero-dimensional perovskite with high-efficiency luminescence and transient response for advanced information encryption - Junheng Yuan; Tianchi Wang; Yu Zhang; Shuyi Yao; Lulu Han; Dedan Mu; Hao Song; Jiayi He; Feng Zhang; Xuhui Xu (Chemical Engineering Journal, 2024)

Comprehensive insights into the impact of magnetic biochar on protein hydrolysis in sludge anaerobic digestion: Protein structures, microbial activities and syntrophic metabolisms - Likui Feng; Huizhi Mu; Zhelu Gao; Tianyi Hu; Shufei He; Yu Liu; Shijie You; Qingliang Zhao; Liangliang Wei (Water Research, 2024)

Multidimensional occurrence and diet risk of emerging contaminants in freshwater with urban agglomerations - Tingting Chai; Yinyin Jin; Feng Cui; Zongjie Li; Mingxiao Li; Shunlong Meng; Lilai Yuan; Jing Qiu; Jiandong Mu; Guohua Xiao; Xiyan Mu; Yongzhong Qian (Journal of Hazardous Materials, 2024)

Hydrothermal-assisted acid-etching of oil shale semi-coke for preparation of mineral/biochar nanocomposites and selective adsorption toward mycotoxins - Feng Zhao; Bin Mu; Yuru Kang; Dandan Wang; Gong Zhu; Aiqin Wang (Journal of Environmental Chemical Engineering, 2024)

Environmental and human history in the hyper-arid eastern Tarim Basin (Lop Nur), northwest China: A critical review for sustaining the natural and cultural landscapes - Kangkang Li; Xiaoguang Qin; Bing Xu; Lei Zhang; Guijin Mu; Yong Wu; Xiaohong Tian; Dong Wei; Chunxue Wang; Huiqiu Shao; Hongjuan Jia; Zhiqiang Yin; et al. (Quaternary International, 2024)

Carbon-dot/attapulgite composite sonocatalytic towards efficient indigo-containing wastewater degradation based on the cavitation mechanism - Yu Chen; Yihe Zhang; Jiahe Zhang; Jiale Zhang; Feng Feng; Bin Mu; Na Zhang (Journal of Water Process Engineering, 2024)

Test and application of abrasion characteristics of brown rice - Xiangyi Meng; Yadong Zhu; Fuguo Jia; Guizhong Tian; Xiaoming Feng; Yongsheng Pei; Zhongqiu Mu (Innovative Food Science & Emerging Technologies, 2024)

A newly isolated halotolerant Rubrivivax gelatinosus MBE with capable of producing hydrogen in the presence of ammonium - Jiali Feng; Xuefang Mu; Shuzhi Zhang; Xiaoyan Shen; Yang Zhou; Shufang Liu; Wen Cao (Biomass and Bioenergy, 2024)

Intelligent Dynamic Warning Method of Rockburst Risk and Level Based on Recurrent Neural Network - Shichao Zhang; Chaomin Mu; Xianhui Feng; Ke Ma; Xiao Guo; Xinsheng Zhang (Rock Mechanics and Rock Engineering, 2024)

Screening and identification of probiotics from the intestinal tract of largemouth bass (Micropterus salmoides) for use as a feed additive and bacterial infection control - Lu Xia; Gaofeng Cheng; Pan Wang; Xinyou Wang; Zhaoran Dong; Qingjiang Mu; Jiaqian Yu; Zhihao Jiang; Jun Xiao; Hao Feng; Xiangping Li; Weiguang Kong; et al. (Aquaculture, 2024)

Method and experimental study of strengthening circular hollow section T-joints by partial filling with cementitious materials - Yifei Wang; Lewei Tong; Feng Zhou; Yinnan Mu; Tiantian Wang (Engineering Structures, 2024)

Inhibiting advanced glycation end products (AGEs) of high-performance hemodialysis membranes self-assembled by gallic acid and Ti3C2Tx MXene - Qiqi Wang; Changjun Mu; Ya'nan Yu; Xia Feng; Yang He; Li Chen (Chemical Engineering Journal, 2024)

Monitoring longitudinal antimicrobial resistance trends of Staphylococcus aureus strains worldwide over the past 100 years to decipher its evolution and transmission - Guan-Yu Fang; Feng-Hua Wu; Xiao-Jing Mu; Yu-Jian Jiang; Xing-Quan Liu (Journal of Hazardous Materials, 2024)

Non-targeted metabolomics identifies biomarkers in milk with high and low milk fat percentage - Xiaofang Feng; Ruoshuang Ma; Ying Wang; Lijia Tong; Wan Wen; Tong Mu; Jia Tian; Baojun Yu; Yaling Gu; Juan Zhang (Food Research International, 2024)

Insights into major pigment accumulation and (non)enzymatic degradations and conjugations to characterized flavors during intelligent black tea processing - Yongcheng Zhang; Kangni Yan; Qunhua Peng; Shan Feng; Zhangfeng Zhao; Long Chen; Lin Ye; Jianyu Fu; Haipeng Lv; Dan Mu; Chunwang Dong; Zhi Lin; et al. (Food Chemistry, 2024)

Dual-use ionization source for direct and sensitive detection of trace carbamates residue - Tong Liu; Guodong Mu; Muyi He; Fengming Chen; Xiuli Xu; Feng Zhang (Food Chemistry, 2024)

Genetically engineering of Saccharomyces cerevisiae for enhanced oral delivery vaccine vehicle - Baoquan Han; Feng Yue; Xiaojun Zhang; Kun Xu; Zhiying Zhang; Zhongyi Sun; Lu Mu; Xiaoyu Li (Fish & Shellfish Immunology, 2024)

The combined effects of microplastics and bisphenol-A on the innate immune system response and intestinal microflora of the swimming crab Portunus trituberculatus - Xiaocong Chen; Shangjie Zhou; Yan Liu; Zhihua Feng; Changkao Mu; Tao Zhang (Aquatic Toxicology, 2024)

Effects of electron acceptors and donors on anaerobic biodegradation of PAHs in marine sediments - Qingguo Chen; Zhenzhen Li; Yu Chen; Mei Liu; Qiao Yang; Baikang Zhu; Jun Mu; Lijuan Feng; Zhi Chen (Marine Pollution Bulletin, 2024)

Ag nanodots-induced interfacial fast electronic/ionic diffusion kinetics of carbon capsule supported CoMn2O4 for high-voltage supercapacitors - Zengcai Guo; Junpeng Wang; Jingbo Mu; Aifeng Liu; Feng Li; Hang Yang; Zhongkai Huang; Yanming Wang (Fuel, 2024)

Screening of anti-allergic Lactiplantibacillus species by splenocyte sensitization model and evaluate their probiotic and postbiotic characteristics - Lu Feng; Zihao Guo; Jinghong Zhao; Wenpu Yao; Xinling Li; Linying Wu; Guangqing Mu; Xuemei Zhu (Food Bioscience, 2024)

Construction of and evaluation of the immune response to two recombinant pseudorabies viruses expressing the B119L and EP364R proteins of African swine fever virus - Xin-Mei Geng; Ying-Mu Xi; Xiang-Mei Huang; Yang-Lin Wang; Xu-Ying Wang; Kang Ouyang; Ying Chen; Zu-Zhang Wei; Yi-Feng Qin; Wei-Jian Huang (Archives of Virology, 2024)

A multidimensional optimization strategy of pyraclostrobin-loaded microcapsules to improve the selectivity between toxicological risk in zebrafish and efficacy in controlling rice blast - Xueping Huang; Jian Luo; Haichao Cao; Aiping Wang; Fengyan Zhou; Feng Liu; Beixing Li; Wei Mu; Yong Zhang (Science of The Total Environment, 2023)

Evaluation of long-term spatio-temporal characteristics of water and nitrogen in the vadose zone and potential threats to groundwater under different irrigation strategies - Jiatun Xu; Qing Mu; Shikun Sun; Nan Yang; Xiongbiao Peng; Yufeng Zou; Shaoyuan Feng; Huanjie Cai (Journal of Cleaner Production, 2023)

An esterase activity-based biosensor for rapid and sensitive detection of viable Escherichia coli O157:H7 in milk - Xiaoyan Feng; Donggen Zhou; Dan Mu; Hengyi Xu (International Dairy Journal, 2023)

Side chain modulated carbazole-based bifunctional hole-shuttle interlayer simultaneously improves interfacial energy level alignment and defect passivation in high-efficiency perovskite solar cells - Yuan-Yu Chiu; Shih-Hsuan Chen; Kun-Mu Lee; Tz-Feng Lin; Ming-Chung Wu (Chemical Engineering Journal, 2023)

Elucidation of the neutralizing antibody evasion of emergent SARS-CoV-2 Omicron sub-lineages using structural analysis - Cong Sun; Yuan-Tao Liu; Yin-Feng Kang; Chu Xie; Shu-Xin Li; Yu-Tong Lu; Mu-Sheng Zeng (Science China Life Sciences, 2023)

Somatic embryo induction and plantlet regeneration of Canna × generalis from immature zygotic embryo - Zu-yan Gan; Mu-lin Shu; Feng Yang; Guo-fang Wang; Wen-e Zhang; Xue-jun Pan (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

Modeling of farmers’ production performance portrait based on GASA-WFCM clustering - Bo Wang; Yan Shi; Weisong Mu; Jianying Feng (Computers and Electronics in Agriculture, 2023)

Nitrogen limitation affects carbon and nitrogen metabolism in mung bean (Vigna radiata L.) - Hang Zhou; Ya Liu; Baomin Mu; Fei Wang; Naijie Feng; Dianfeng Zheng (Journal of Plant Physiology, 2023)

Geochronology and in-situ apatite geochemistry of late Paleoproterozoic A-type granites in the Jiao-Liao-Ji Belt, North China Craton: Implications for petrogenesis and tectonic evolution - Yi-Kang Quan; Mao-Song Mu; De-Bin Yang; Xiang-Yu Yan; An-Qi Wang; Le-Ran Hao; Feng Wang (Geochemistry, 2023)

In situ interfacial engineering modulated adsorption and electron transfer boosting peroxymonosulfate activation for micro-contaminates degradation over CoOx nanosheet - Jinming Feng; Jincheng Mu; Qiong Peng; Yang Xiao; Baojun Liu (Chemical Engineering Journal, 2023)

The regulative effect and repercussion of probiotics and prebiotics on osteoporosis: involvement of brain-gut-bone axis - Yuan-Wei Zhang; Mu-Min Cao; Ying-Juan Li; Guang-Chun Dai; Pan-Pan Lu; Ming Zhang; Li-Yong Bai; Xiang-Xu Chen; Cheng Zhang; Liu Shi; Yun-Feng Rui (Critical Reviews in Food Science and Nutrition, 2023)

Study on the seismic mitigation effects of inerter isolated storage tanks - Chao Luo; Haoran Mu; Hao Wang; Xiaoxia Guo; Donglin Liu; Huaiping Feng (Soil Dynamics and Earthquake Engineering, 2023)

Enhanced hydrophobic microporous Pt/silica with high adsorption and catalytic oxidation for trace toluene removal - Mu Zhou; Shuangde Li; Mengjie Cao; Tao Wang; Linfeng Nie; Weiman Li; Feng Zhao; Yunfa Chen (Journal of Environmental Chemical Engineering, 2023)

Emission factors and source profiles of VOCs emitted from coke production in Shanxi, China - Ling Mu; Chuanyang Feng; Yangyong Li; Xiaofan Li; Tian Liu; Xin Jiang; Ziye Liu; Huiling Bai; Xiaofeng Liu (Environmental Pollution, 2023)

Highly active complexes of pyrite and organic matter regulate arsenic fate - Shuting Wang; Jingyu Wen; Li Mu; Xiangang Hu; Ruihong Feng; Yuying Jia (Journal of Hazardous Materials, 2023)

Leukocyte subtype classification with multi-model fusion - Yingying Ding; Xuehui Tang; Yuan Zhuang; Junjie Mu; Shuchao Chen; Shanshan Liu; Sihao Feng; Hongbo Chen (Medical & Biological Engineering & Computing, 2023)

Delamination of multilayer Ti3C2T MXene alters its adsorpiton and reduction of heavy metals in water - Yuxuan Zhang; Jun Luo; Biao Feng; Hongxia Xu; Yuanyuan Sun; Xueyuan Gu; Xin Hu; Mu Naushad; Bin Gao; Hongqiang Ren (Environmental Pollution, 2023)

Distribution characteristics of secondary organic aerosol tracers in PM2.5 in Jinzhong - Ling Mu; Xin Jiang; Yangyong Li; Xuemei Li; Xiaofan Li; Tian Liu; Ziye Liu; Chuanyang Feng (Atmospheric Environment, 2023)

Machine learning improves prediction of severity and outcomes of acute pancreatitis: a prospective multi-center cohort study - Jia-Ning Li; Dong Mu; Shi-Cheng Zheng; Wei Tian; Zuo-Yan Wu; Jie Meng; Rui-Feng Wang; Tian-Lei Zheng; Yue-Lun Zhang; John Windsor; Guo-Tao Lu; Dong Wu (Science China Life Sciences, 2023)

Short-chain fatty acids (SCFAs) as potential resuscitation factors that promote the isolation and culture of uncultured bacteria in marine sediments - Chun-Shui Sun; Liu-Yan Zhou; Qi-Yun Liang; Xiao-Man Wang; Yi-Xuan Lei; Zhen-Xing Xu; Feng-Qing Wang; Guan-Jun Chen; Zong-Jun Du; Da-Shuai Mu (Marine Life Science & Technology, 2023)
Many marine bacteria are difficult to culture because they are dormant, rare or found in low-abundances. Enrichment culturing has been widely tested as an important strategy to isolate rare or dormant microbes. However, many more mechanisms remain uncertain. Here, based on 16S rRNA gene high-throughput sequencing and metabolomics technology, it was found that the short-chain fatty acids (SCFAs) in metabolites were significantly correlated with uncultured bacterial groups during enrichment cultures. A pure culture analysis showed that the addition of SCFAs to media also resulted in high efficiency for the isolation of uncultured strains from marine sediments. As a result, 238 strains belonging to 10 phyla, 26 families and 82 species were successfully isolated. Some uncultured rare taxa within Chlorobi and Kiritimatiellaeota were successfully cultured . Amongst the newly isolated uncultured microbes, most genomes, e.g. bacteria, possess SCFA oxidative degradation genes, and these features might aid these microbes in better adapting to the culture media. A further resuscitation analysis of a viable but non-culturable (VBNC) Marinilabiliales strain verified that the addition of SCFAs could break the dormancy of Marinilabiliales in 5 days, and the growth curve test showed that the SCFAs could shorten the lag phase and increase the growth rate. Overall, this study provides new insights into SCFAs, which were first studied as resuscitation factors in uncultured marine bacteria. Thus, this study can help improve the utilisation and excavation of marine microbial resources, especially for the most-wanted or key players.

Aging of pollution air parcels acts as the dominant source for nocturnal HONO - Wenjin Zhang; Yangang Ren; Chenglong Zhang; Pengfei Liu; Chaoyang Xue; Can Ye; Chengtang Liu; Jinhe Wang; Yuanyuan Zhang; Junfeng Liu; Yifei Song; Yinchang Feng; et al. (Science of The Total Environment, 2023)

Obtaining mutant Chlorella vulgaris strains with excellent self-flocculation properties and high wastewater treatment efficiency via atmospheric and room temperature plasma technique - Guixia Ma; Qianya Meng; Ruimin Mu; Feng Qi; Xihan Wang (Journal of Water Process Engineering, 2023)

Composition and transcriptional activity of oil reservoir microorganisms under different gas/liquid ratios - Li-Bin Shou; Zhao-Wei Hou; Yi-Fan Liu; Ying Wang; Lei Zhou; Jin-Feng Liu; Shi-Zhong Yang; Ji-Dong Gu; Xiao-Lin Wu; Bo-Zhong Mu (International Biodeterioration & Biodegradation, 2023)

Identification of sweet spots in shale-type and siltstone-type “shale oil systems”: A case study of the Chang 7 Member in Ordos Basin - Songqi Pan; Qiulei Guo; Caineng Zou; Zhenhua Jing; Ming Yuan; Ying He; He Zheng; Ying Mu; Zhi Yang; Shixiang Li; Xinping Zhou; Songtao Wu; et al. (Science China Earth Sciences, 2023)

Characteristics and source apportionment of water-soluble inorganic ions in atmospheric particles in Lvliang, China - Tian Liu; Ling Mu; Xiaofan Li; Yangyong Li; Ziye Liu; Xin Jiang; Chuanyang Feng; Lirong Zheng (Environmental Geochemistry and Health, 2023)

In-depth understanding of the deterioration mechanism and modification engineering of high energy density Ni-rich layered lithium transition-metal oxide cathode for lithium-ion batteries - Lijuan Hou; Qi Liu; Xinyuan Chen; Qiang Yang; Daobin Mu; Li Li; Feng Wu; Renjie Chen (Chemical Engineering Journal, 2023)

Association between urinary cadmium level and subclinical myocardial injury in the general population without cardiovascular disease aged ≥ 50 years - Yu-Jie Wu; Si-Bo Wang; Jia-Teng Sun; Ling-Feng Gu; Ze-Mu Wang; Bo Deng; Hao Wang; Lian-Sheng Wang (Environmental Science and Pollution Research, 2023)

Comparative genomics reveal distinct potential of Tamlana sp. S12 for algal polysaccharide degradation - Hai-Feng Xia; Xiao-Yu Jia; Yan-Xia Zhou; Zong-Jun Du; Da-Shuai Mu; Guan-Jun Chen (Frontiers in Marine Science, 2023)
Introduction Macroalgae contain various polysaccharides that serve as nutrient sources Introduction: Macroalgae contain various polysaccharides that serve as nutrient sources for marine bacteria. Carbohydrate-active enzymes (CAZymes) are the primary feature of marine bacteria that utilize these polysaccharides. In this study, we describe Tamlana sp. S12, a novel strain of marine flavobacteria that can degrade alginate and Laminaria japonica biomass, isolated from the intestines of the sea cucumber Apostichopus japonicas collected at Weihai coast. Methods We sequenced the entire genome of strain S12 and constructed a phylogenetic tree using the core genome sequences of related strains. We determined the enzymatic activity of strain S12 using the DNS method and measured its growth curve under different carbon sources using spectrophotometry. Results Strain S12 degraded dehydrated L. japonica fragments as the sole nutrient source within 48h. Strain S12 harbors a diverse array of CAZymes at multiple polysaccharide utilization loci (PUL). One PUL encoding lyases from PL6, 7, and 17 families may be used for the degradation of alginate. Additionally, strain S12 harbors PULs encoding carrageenan- and agar-targeting CAZymes. Comparative analysis with related flavobacteria from Algibacter , Maribacter , and Zobellia showed shared CAZymes among these strains, potentially derived from a common ancestor and stably maintained within strains. Genomic signatures, algal degradation ability, and CAZyme patterns suggest that strain S12 has the potential to degrade complex algal polysaccharides. Conclusion These results expand our knowledge of CAZymes and enrich our understanding of how marine Flavobacteriaceae adapt to marine algal polysaccharide environments. The availability of the genome of Tamlana sp. S12 will be beneficial for further analyses of marine Flavobacteriaceae.

Study on fatty acid binding protein in lipid metabolism of livestock and poultry - Chuanchuan Wang; Tong Mu; Xiaofang Feng; Juan Zhang; Yaling Gu (Research in Veterinary Science, 2023)

Autochthonous bioaugmentation accelerates phenanthrene degradation in acclimated soil - Haiping Gu; Jie Yan; Yuhao Liu; Xuewei Yu; Yan Feng; Xuanyi Yang; Su Shiung Lam; Mu. Naushad; Cheng Li; Christian Sonne (Environmental Research, 2023)

Interactions between dissolved organic matter and the microbial community are modified by microplastics and heat waves - Zhongwei Wang; Xiangang Hu; Weilu Kang; Qian Qu; Ruihong Feng; Li Mu (Journal of Hazardous Materials, 2023)

ROS filter coating scaffold protects 3D mesenchymal stem cell spheroids for dual-phase treatment of spinal cord injury - Jian Cao; Jiahe Wu; Jiafu Mu; Lingmin Lin; Xunqi Zhang; Tianchen Huang; Teng Ma; Manning Zhu; Xiaoyang Dai; Xuhua Wang; Shiqing Feng; Jian-Qing Gao (Chemical Engineering Journal, 2023)

Cation mixing effect regulation by niobium for high voltage single-crystalline nickel-rich cathodes - Zhikun Zhao; Chunli Li; Ziyue Wen; Zhuolin Yang; Shijie Lu; Xinyu Zhang; Shi Chen; Borong Wu; Feng Wu; Daobin Mu (Chemical Engineering Journal, 2023)

Efficient removal of trace uranium from nuclear effluents using irradiation-functionalized fibrous adsorbents with very high salt tolerance - Yulong He; Liuhua Mu; Minglei Wang; Lijun Hu; Wanning Ren; Xuanzhi Mao; Xinxin Feng; Mingxing Zhang; Rong Li; Zhe Xing; Jiangtao Hu; Guozhong Wu (Chemical Engineering Journal, 2023)

Targeting Senescent Tendon Stem/Progenitor Cells to Prevent or Treat Age-Related Tendon Disorders - Hao Wang; Guang-Chun Dai; Ying-Juan Li; Min-Hao Chen; Pan-Pan Lu; Yuan-Wei Zhang; Ming -Zhang; Mu-Min Cao; Yun-Feng Rui (Stem Cell Reviews and Reports, 2023)

Gully erosion and expansion mechanisms in loess tablelands and the scientific basis of gully consolidation and tableland protection - Zhao Jin; Jianbing Peng; Jianqi Zhuang; Li Feng; Aidi Huo; Xingmin Mu; Wenlong Wang (Science China Earth Sciences, 2023)

Ecological carrying capacity and carbon sequestration potential of bivalve shellfish in marine ranching: A case study in Bohai Bay, China - Zepeng Li; Yan Chen; Gang Wang; Jiandong Mu; Yanfeng Sun; Haolin Yu; Jiangling Xu; Ying Yan; Shuangyue Luo; Fuqiang Han; Jie Feng; Zhe Pan (Frontiers in Marine Science, 2023)
Introduction Shellfish play an important role in ecological restoration and as carbon (C) sinks, but studies on their ecological carrying capacity (ECC) and C sequestration potential are sparse. Methods In this study, we selected a 57-hectare artificial oyster reef in a typical marine ranching in Bohai Bay, China, to evaluate the ECC and their C sequestration potential of bivalve shellfish, and projecting their impact on functional groups in the system, with an Ecopath with Ecosim (EwE) food web model. We conducted four biological surveys to obtain the biomass measurements, with one conducted in each of the summer, autumn, and winter of 2019 and one in the spring of 2020; and the functional groups included in the surveys comprised fish, cephalopods, crustaceans, snails, bivalve shellfish, annelids, other macrobenthos, meiobenthos, starfish, sea cucumbers, zooplankton, phytoplankton, and detritus. Results and Discussion The EwE model prediction results showed that the ECC of bivalve shellfish was established to be 282.66 t/km 2 , far more than the existing quantity of 187.76 t/km 2 . Therefore, at present, the ecosystem of the study marine ranching is not yet mature. Moreover, our ecological network analysis parameters indicated that the marine ranching ecosystem will be mature and stable when the bivalve shellfish population reaches its ECC. However, the increase in bivalve shellfish biomass will result in a decrease in the population sizes of species competing for food resources with bivalve shellfish, mainly gobiid fish such as Tridentiger bifasciatus, Tridentiger trigonocephalus, Tridentiger barbatus . Simultaneously, when the bivalve shellfish reach their ECC, 29.23 t of CO 2 can be sequestrated by bivalve shellfish, comprising 14.32 t being removed from the ecosystem as prey and 14.91 t being stored on the seafloor through biodeposition. Conclusion Therefore, the research demonstrated that, within the scope of ECC, the increasing bivalve shellfish can improve the C sequestration capacity of the marine ranch ecosystem, and effective management of bivalve shellfish in marine ranching can improve the economic benefits and C sink service functions of marine ranching.

Bifunctional electrocatalyst junction engineering: CoP nanoparticles in-situ anchored on Co3(Si2O5)2(OH)2 nanosheets for highly efficient water splitting - Yang Mu; Yifu Zhang; Ziyi Feng; Xueying Dong; Xuyang Jing; Xiaoyu Pei; Yunfeng Zhao; Zongkui Kou; Changgong Meng (Chemical Engineering Journal, 2023)

Adsorption behaviour and mechanism of Avermectin-based pesticides in soil driven by H-bonds formed between the compounds and humus - Tong-fang Jing; Da-xia Zhang; Yao-zhong Zhang; Yan Jin; Xian-zheng Han; Wei Mu; Bei-xing Li; Feng Liu (Chemical Engineering Journal, 2023)

Oxygen vacancy boosting peroxymonosulfate activation over nanosheets assembled flower-like CoMoO4 for contaminant removal: Performance and activity enhancement mechanisms - Jincheng Mu; Jinming Feng; Xinyang Wang; Baojun Liu (Chemical Engineering Journal, 2023)

Bidirectional reflectance factor measurement of conifer needles with microscopic spectroscopy imaging - Yongkang Lai; Xihan Mu; Yuequn Bian; Xiaohan Dong; Feng Qiu; Xinyu Bo; Zhixiang Zhang; Yi Li; Xinli Liu; Linyuan Li; Donghui Xie; Guangjian Yan (Agricultural and Forest Meteorology, 2023)

Liquid metal @ mxene spring supports ionic gel with excellent mechanical properties for high-sensitivity wearable strain sensor - Lisong Dong; Xiaoyao Zhou; Shuxin Zheng; Zhongfan Luo; Yuxiang Nie; Xin Feng; Jiahua Zhu; Zhangzhong Wang; Xiaohua Lu; Liwen Mu (Chemical Engineering Journal, 2023)

Humic acid nature and compound structure together determine the capacity of soil to sorb Avermectin B1a and its derivatives - Tong-fang Jing; Da-xia Zhang; Yan Jin; Guo-dong Si; Bei-xing Li; Wei Mu; Feng Liu (Chemical Engineering Journal, 2023)

Ship Dynamic Positioning Output Feedback Control with Position Constraint Considering Thruster System Dynamics - Dongdong Mu; Yupei Feng; Guofeng Wang; Yunsheng Fan; Yongsheng Zhao; Xiaojie Sun (Journal of Marine Science and Engineering, 2023)
In order to simultaneously address the issues of ship operating area limitation, unknown time-varying disturbances, immeasurable ship speed, unknown dynamics, and input saturation, this paper investigates the position-constrained ship dynamic positioning output feedback control, taking thruster system dynamics into account. Firstly, a barrier Lyapunov function (BLF) is utilized to limit the ship position inside the dynamic positioning system’s acceptable working range and to limit the ship position error. Second, the set total disturbance, which is made up of unknown time-varying disturbances and unknown dynamics and is further handled by the control strategy, is estimated using a fixed-time extended state observer (FDESO). Additionally, the thruster system dynamics equations are incorporated into the controller design process so that the generated thrust signal varies gradually without abrupt fluctuations, in keeping with engineering realities. Furthermore, the thruster input saturation issue is dealt with using a finite-time auxiliary dynamic system. Finally, a robust control term is introduced to handle the errors generated in the controller design. The stability proof section demonstrates that the designed control strategy can cause the ship to arrive and maintain at the desired location and heading, as well as stay continuously inside the designated operating area with all signals of the closed-loop control system being consistently and eventually bounded. The simulation results demonstrate that the proposed system is valid.

Exposure of zebrafish (Danio rerio) to trans-2-hexenal induces oxidative stress and protein degeneration of the gill - Dicheng Ma; Haiyan Yu; Guangrui Cui; Jiamei Zhu; Bingyu Zhu; Wei Mu; Feng Liu (Science of The Total Environment, 2023)

Experimental and numerical simulation study on mechanical properties of fiber-reinforced plastic seismic isolator - Hao Wang; Haoran Mu; Xiaoxia Guo; Yunfei Zhang; Haowei Ji; Chao Luo; Huaiping Feng; Donglin Liu (Engineering Structures, 2023)

Balance the rapid release of insecticide microcapsules using double-layer shielding effect when the foliar application - Rui Wang; Song Liu; Feng-shou Sun; Xin Yu; Xiao Liu; Bei-xing Li; Wei Mu; Da-xia Zhang; Feng Liu (Chemical Engineering Journal, 2023)

In-situ Fe/Ti doped amine-grafted silica aerogel from fly ash for efficient CO2 capture: Facile synthesis and super adsorption performance - Lingyuan Fan; Yuanqiong Mu; Jiali Feng; Fangqin Cheng; Mei Zhang; Min Guo (Chemical Engineering Journal, 2023)

Longitudinal expression profiles of flavonoid synthesis-related genes and their correlations with contents of flavonoids including anthocyanins in purplish-green aerial stems of Panax notoginseng - Hongling Zhang; Guiqiong Li; Min Jiang; Changling Zhao; Pengyu Zhao; Chen Wang; Guosong Wen; Feng Zhou; Wenhua Dongchen; Shaozhong Xu; Ting Mu; Fanlai Meng; et al. (Acta Physiologiae Plantarum, 2023)

An association study on the risk, glucocorticoids effectiveness, and prognosis of systemic lupus erythematosus: insight from mitochondrial DNA copy number - Zhen Li; Qi-Qun Zong; Chun-Xia Zhai; Guang-Hui Yu; Wan-Qin Hu; Yu-Hua Wang; Lin-Lin Wang; Zi-Ye Yan; Ting-Yu Zhang; Ying Teng; Shuang Liu; Jing Cai; et al. (Immunologic Research, 2022)

Fine mapping of powdery mildew and stripe rust resistance genes Pm5V/Yr5V transferred from Dasypyrum villosum into wheat without yield penalty - Ruiqi Zhang; Chuntian Lu; Xiangru Meng; Yali Fan; Jie Du; Runran Liu; Yigao Feng; Liping Xing; Petr Cápal; Kateřina Holušová; Jaroslav Doležel; Yiwei Wang; et al. (Theoretical and Applied Genetics, 2022)

Checking transformation efficiency for different Lagenaria siceraria genotypes by using seed germination pouches as a growth carrier - Ying Wang; Lijuan Huang; Yanwei Li; Zishan Feng; Zihan Mu; Jian Wang; Xinyi Wu; Baogen Wang; Zhongfu Lu; Guojing Li; Xiaohua Wu (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)
Bottle gourd [ Lagenaria siceraria (Mol.) Standl.] is one of the most common horticultural and medicinal crops. Genetic transformation is a rate-limiting step in unraveling the function of genes and molecular breeding in this non-model crop. In this study, we established an optimized protocol for transformation using a seed germination pouch as a growth carrier and developed bottle gourd composite plants. Overground explants were inoculated with Agrobacterium rhizogenes strain R1000, which harbored a binary vector pBI121 carrying the GUS reporter gene. The integration of GUS into transgenic roots was confirmed via reverse transcription-polymerase chain reaction and histochemical staining. Furthermore, we screened for desirable genotypes from 14 bottle gourd germplasm collections based on the number of induced roots, transformation efficiency, and induction rate, and “Changguang” (transformation efficiency, approximately 36.8%) was selected as the genotype suitable for hairy root induction in bottle gourd. The optimized protocol presented here is a rapid, suitable, and efficient tool for studying the function of genes and root biology of bottle gourd in the future.

Studies on the Physiological Mechanism of Brassinolide to Improve the Resistance of Rice Seedlings to NaCl Stress - Dewei Mu; Naijie Feng; Dianfeng Zheng; Hang Zhou; Ling Liu; Guanjie Chen (Water, Air, & Soil Pollution, 2022)

Discovery of the non‐cosmopolitan lineages in Candidatus Thermoprofundales - Yi‐Fan Liu; Liu Yang; Zhong‐Lin Liu; Jing Chen; Bo Fang; Lei Zhou; Jin‐Feng Liu; Shi‐Zhong Yang; Ji‐Dong Gu; Bo‐Zhong Mu (Environmental Microbiology, 2022)
Summary The recently proposed order Candidatus Thermoprofundales, currently containing only one family‐level lineage Marine Benthic Group‐D (MBG‐D), is distributed in global subsurface ecosystems and ecologically important, but its diversity, evolution and metabolism remain largely unknown. Here we described two novel family‐level specialized lineages in Ca . Thermoprofundales, JdFR‐43 and HyVt, which are restricted to specific biotopes (primarily in marine hydrothermal vents and occasionally in oil reservoirs and hot springs) in contrast to the cosmopolitan lineage MBG‐D. The comparative genomics revealed that the specialized lineages have streamlined genomes, higher GC contents, enriched genes associated with nucleotide biosynthesis, ribosome biogenesis and DNA repair and additional thermostable aminopeptidases, enabling them to adapt to high‐temperature habitats such as marine hydrothermal vents, deep subsurface oil reservoirs and hot springs. On the contrary, the unique metabolic traits of the cosmopolitan MBG‐D, motility, glycolysis, butanoate metabolism, secondary metabolites production and additional genes for specific peptides and carbohydrates degradation potentially enhance its response to environmental change. Substrate preference is found for most MAGs across all lineages with the ability to utilize both polysaccharides (chitin and starch) and proteinaceous substances, whereas JdFR‐43 members from oil reservoirs can only utilize proteins. These results expand the diversity of C a . Thermoprofundales significantly and further improve our understandings of the adaptations of C a . Thermoprofundales to various environments.

A new highly oxygenated germacranolide from Carpesium nepalense var. lanatum (C.B.Clarke) Kitam - Yi-Fan Yu; Yue-Qian Li; Ru-Yue Wang; Xu Liu; Wen-Bo Cui; Xiao-Han Chen; Cheng-Mu Zhao; Feng-Ming Qi; Zhan-Xin Zhang; Dong-Qing Fei (Natural Product Research, 2022)

Salt intake and gastric cancer: a pooled analysis within the Stomach cancer Pooling (StoP) Project - Samantha Morais; Adriana Costa; Gabriela Albuquerque; Natália Araújo; Claudio Pelucchi; Charles S. Rabkin; Linda M. Liao; Rashmi Sinha; Zuo-Feng Zhang; Jinfu Hu; Kenneth C. Johnson; Domenico Palli; et al. (Cancer Causes & Control, 2022)

Stability analysis of check dam impacted by intermittent surge - Daochuan Liu; Yong You; Jinfeng Liu; Qi Mu; Jin Feng; Lei Zhang; Anhui Wei; Huafu Tan (Bulletin of Engineering Geology and the Environment, 2022)

Disaster characteristics and influence range of earth fissure on nearby structures - Yahong Deng; Jiang Chang; Quanzhong Lu; Li Li; Huandong Mu; Libin Feng (Arabian Journal of Geosciences, 2022)

Survival and Metabolic Modulation of Swimming Crab Portunus trituberculatus During Live Transport - Ce Shi; Yangfang Ye; Feng Pei; Changkao Mu; Chunlin Wang (Frontiers in Marine Science, 2021)
Demand from consumers for small quantities of live swimming crab Portunus trituberculatus is rising with the development of e-commerce. However, it is challenging to keep P. trituberculatus alive post-capture. In this study, a transport bag containing oxygen and seawater (24 ppt) was used to investigate the survival and metabolic changes of P. trituberculatus during transport. The results showed that more than 80% P. trituberculatus could survive at least 24 h in the transport bag. The ability of the crabs to survive may be attributed to adaptive metabolism, as suggested by the switch from an aerobic to an anaerobic pathway for energy generation and a decline in amino acid metabolism, nucleic acid metabolism, and osmoregulation. Our findings suggest that the transport bag could effectively extend the post-capture survival time of P. trituberculatus . Metabolic adaptation – especially energy homeostasis – is crucial for crab survival during transport. Our study provides a promising method for the transport of live P. trituberculatus .

Experimental study on the suffusion mechanism of gap-graded soils under an exceedance hydraulic gradient - Liang Chen; Yu Wan; Jian-Jian He; Chun-Mu Luo; Shu-Fa Yan; Xian-Feng He (Natural Hazards, 2021)

A landslide in Heifangtai, northwest of the Chinese Loess Plateau: triggered factors, movement characteristics, and failure mechanism - Jia-xu Kong; Jian-qi Zhuang; Jie-wei Zhan; Zheng-wei Bai; Yan-qiu Leng; Peng-hui Ma; Jian-bing Peng; Zuo-peng Wang; Tian-feng Gu; Jia-xing Sun; Fan-chen Zhang; Yuan-jun Xu; et al. (Landslides, 2021)

Low-Se Diet Can Affect Sperm Quality and Testicular Glutathione Peroxidase-4 activity in Rats - Qin Wang; Shuo Zhan; Yiqun Liu; Feng Han; Lili Shi; Chao Han; Weipeng Mu; Jizhong Cheng; Zhen-wu Huang (Biological Trace Element Research, 2021)

Detecting Regional Deep Ocean Warming below 2000 meter Based on Altimetry, GRACE, Argo, and CTD Data - Yuanyuan Yang; Min Zhong; Wei Feng; Dapeng Mu (Advances in Atmospheric Sciences, 2021)

Flavonoids from Artemisia rupestris and their synergistic antibacterial effects on drug-resistant Staphylococcus aureus - Jiang-Er Lan; Xiao-Jin Li; Xiao-Feng Zhu; Zhong-Lin Sun; Jian-Ming He; Mire Zloh; Simon Gibbons; Qing Mu (Natural Product Research, 2021)

Numerical Analysis of the Water-blocking Performance of a Floor with a Composite Structure under Fluid–solid Coupling - Ang Li; Qian Mu; Li Ma; Chaoyang Liu; Shengquan Wang; Feng Wang; Lin Mou (Mine Water and the Environment, 2021)

Dissipation kinetics and safety evaluation of pyraclostrobin and its desmethoxy metabolite BF 500-3 in a cucumber greenhouse agroecosystem - Lifei He; Falin He; Song Yang; Yangyang Gao; Beixing Li; Feng Liu; Wei Mu (Environmental Science and Pollution Research, 2021)

Serum Ceruloplasmin Is the Candidate Predictive Biomarker for Acute Aortic Dissection and Is Related to Thrombosed False Lumen: a Propensity Score–Matched Observational Case–Control Study - Changcheng Ma; Haibin Zhao; Feng Shi; Mu Li; Xun Liu; Chao Ji; Yanshuo Han (Biological Trace Element Research, 2021)

Quantitative Determination of Trace Lipopeptide Using HPLC through Double Carboxyls Labelling - Shi-Zhong Yang; Hong-Zhi Quan; Jin-Feng Liu; Hong-Ze Gang; Bo-Zhong Mu (International Journal of Peptide Research and Therapeutics, 2020)

Performance, kinetics characteristics and enhancement mechanisms in anammox process under Fe(II) enhanced conditions - Si-min Tang; Ze-hao Xu; Ya-lei Liu; Guang-feng Yang; Jun Mu; Ren-cun Jin; Qiao Yang; Xiao-ling Zhang (Biodegradation, 2020)

Creation of fertility-restored materials for Ogura CMS in Brassica oleracea by introducing Rfo gene from Brassica napus via an allotriploid strategy - Hai-long Yu; Zhi-yuan Li; Wen-jing Ren; Feng-qing Han; Li-mei Yang; Mu Zhuang; Hong-hao Lv; Yu-mei Liu; Zhi-yuan Fang; Yang-yong Zhang (Theoretical and Applied Genetics, 2020)
Key message Ogura CMS fertility-restored materials, with 18 chromosomes, normal seed setting, stable fertility and closer genetic background to the parent Chinese kale, were successfully developed in B. oleracea via a triploid strategy for the first time. Abstract Ogura cytoplasmic male sterility (CMS) is the most widely used sterile type in seed production for commercial hybrids of Brassica oleracea vegetables. However, the natural Ogura CMS restorer line has not been found in B. oleracea crops. In this study, the triploid strategy was used with the aim to create euploid B. oleracea progenies with the Rfo gene. The allotriploid AAC hybrid YL2 was used as a male parent to backcross with Ogura CMS Chinese kale. After successive backcrosses, the BC 2 Rfo -positive individual 16CMSF2-11 and its BC 3 progenies, with 18 chromosomes, were developed, which were morphologically identical to the parent Chinese kale. Compared with F 1 and BC 1 plants, it showed stable fertility performance, and regular meiosis behavior and could produce seeds normally under natural pollination. The genomic composition analysis of Rfo -positive progenies by using molecular markers showed that more than 87% of the C-genome components of BC 3 Rfo -progenies recovered to the parent Chinese kale, while most or all of the A n -genome segments were lost in 16CMSF2-11 and its progenies. The results suggested that the genetic background of Rfo -positive individuals was closer to that of the parent Chinese kale along with backcrossing. Hereof, the Ogura CMS fertility-restored materials of Chinese kale were successfully created via triploid strategy for the first time, providing a bridge for utilizing the Ogura CMS B. oleracea germplasm in the future. Moreover, our study indicates that the triploid strategy is effective for transferring genes from B. napus into B. oleracea .

The anti-inflammatory drug dimethyl itaconate protects against colitis-associated colorectal cancer - Qian Wang; Xin Ling Li; Yan Mei; Jia-Chong Ye; Wei Fan; Guang-Hui Cheng; Mu-Sheng Zeng; Guo-Kai Feng (Journal of Molecular Medicine, 2020)

Dual-Emitting N/S-Doped Carbon Dots-Based Ratiometric Fluorescent and Light Scattering Sensor for High Precision Detection of Fe(III) Ions - Zhiyan Chen; Xueqin Xu; Dongling Meng; Honglin Jiang; Yun Zhou; Shouai Feng; Zhao Mu; Yaling Yang (Journal of Fluorescence, 2020)

Vitamin D receptor gene methylation in patients with hand, foot, and mouth disease caused by enterovirus 71 - Ya-Ping Li; Hui-Ling Deng; Wen-Jun Wang; Mu-Qi Wang; Mei Li; Yu-Feng Zhang; Jun Wang; Shuang-Suo Dang (Archives of Virology, 2020)

Efficacy of fluopyram as a candidate trunk-injection agent against Bursaphelenchus xylophilus - Guangying Liu; Xu Lin; Shuangyu Xu; Guang Liu; Zhenyu Liu; Feng Liu; Wei Mu (European Journal of Plant Pathology, 2020)

Recent progress on the molecular breeding of Cucumis sativus L. in China - Shengjun Feng; Juping Zhang; Zihan Mu; Yuji Wang; Changlong Wen; Tao Wu; Chao Yu; Zheng Li; Huasen Wang (Theoretical and Applied Genetics, 2020)

Acceleration of thaw slump during 1997–2017 in the Qilian Mountains of the northern Qinghai-Tibetan plateau - Cuicui Mu; Jianguo Shang; Tingjun Zhang; Chengyan Fan; Shufa Wang; Xiaoqing Peng; Wen Zhong; Feng Zhang; Mei Mu; Lin Jia (Landslides, 2020)

Decreased mRNA Expressions of CD40L in Patients with Neuromyelitis Optica Spectrum Disorder - Ziyan Shi; Ling Feng; Zhiyun Lian; Ju Liu; Hongxi Chen; Qin Du; Ying Zhang; Qin Zhang; Mu Yang; Hongyu Zhou (Journal of Molecular Neuroscience, 2020)

Performance and Spatial Distribution of Functional Bacteria under Low-Temperature Stress in Biofilm Systems for Polluted Source Water Pretreatment - Guang-feng Yang; Li-juan Feng; Jun Mu; Jing-ya Sun; Liang Zhu; Xiang-yang Xu (International Journal of Environmental Research, 2019)

A Novel Application of Fluorine Doped Carbon Dots Combining Vortex-Assisted Liquid-Liquid Microextraction for Determination of 4-Nitrophenol with Spectrofluorimetric Method - Shouai Feng; Zhao Mu; Hong Liu; Jiangfeng Huang; Xiaolan Li; Yaling Yang (Journal of Fluorescence, 2019)

Geosites in Karamay city, Xinjiang Uygur Autonomous Region, northwest China - Jun-Ting Qiu; Liang Qiu; Hong-Xu Mu; Wen-Xin Yang; Feng Chen; Bo-Kun Yan; Jun-Chuan Yu; He-Ming Yang (Geoheritage, 2019)

The carbon source separation from fermented sewage sludge for stimulation of denitrification and bisphenol A removal - R. Jia; L. J. Feng; G. F. Yang; J. Mu (International Journal of Environmental Science and Technology, 2019)

Pseudomonas monteilii PN1: a great potential P-nitrophenol degrader with plant growth promoting traits under drought and saline–alkali stresses - Yuqin Zhang; Feng Yang; Hejun Ren; Jinliang Liu; Wenyang Mu; Yan Wang (Biotechnology Letters, 2019)

Pedobacter pollutisoli sp. nov., Isolated from Tetrabromobisphenol A-Contaminated Soil - Yang Mu; Zhuang Ke; Chen-Xi Feng; Xiao-Wei Wang; Xiao-Wen Wang; Hong-Mei Wang; Qing Chen; Jian He (Current Microbiology, 2019)

Calculation of an Adequate Intake (AI) Value and Safe Range of Selenium (Se) for Chinese Infants 0–3 Months Old Based on Se Concentration in the Milk of Lactating Chinese Women with Optimal Se Intake - Feng Han; Liping Liu; Jiaxi Lu; Yingjuan Chai; Jie Zhang; Shijin Wang; Licui Sun; Qin Wang; Yiqun Liu; Mengjie He; Weipeng Mu; Zhenwu Huang (Biological Trace Element Research, 2019)

Atorvastatin ameliorates the contractile dysfunction of the aorta induced by organ culture - Feng Zhou; Fang Rao; You-Qing Deng; Hui Yang; Su-Juan Kuang; Fei-Long Wu; Shu-Lin Wu; Yu-Mei Xue; Xiao-Mu Wu; Chun-Yu Deng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2019)

Base cation concentrations in forest litter and topsoil have different responses to climate and tree species along elevational gradients - Feng Xue; Ming-fei Zhao; Yu-hang Wang; Mu-yi Kang; Kai-xiong Xing; Guo-yi Wang; Jing-jing Shi; Chen Chen; Yuan Jiang (Journal of Mountain Science, 2019)

A new insight into lead (II) tolerance of environmental fungi based on a study of Aspergillus niger and Penicillium oxalicum - Da Tian; Zhongquan Jiang; Liu Jiang; Mu Su; Zheye Feng; Lin Zhang; Shimei Wang; Zhen Li; Shuijin Hu (Environmental Microbiology, 2019)
Summary Environmental microorganisms have been widely applied in heavy metal remediation. This study explored the mechanisms of lead tolerance of two typical filamentous fungi, Aspergillus niger and Penicillium oxalicum . It is shown that the mechanisms of reducing Pb toxicity by these two fungi have three major pathways. The secreted oxalic acid can react with Pb (II) to form insoluble Pb minerals, primarily lead oxalate. Then, the enhanced biosorption via forming new border of cell wall prevents the transportation of Pb (II) into hypha. In addition, the fungal activity could be maintained even at high Pb concentration due to the intracellular accumulation. It was confirmed that A. niger has the higher Pb tolerance (up to 1500 mg l −1 Pb level) compared with P. oxalicum (up to 1000 mg l −1 ). Meanwhile, Pb levels below 1000 mg l −1 partially stimulate the bioactivity of A. niger , which was confirmed by its elevated respiration (from 53 to 63 mg C l −1 medium h −1 ). This subsequently enhanced microbial functions of A. niger to resist Pb toxicity. A better understanding of Pb tolerance of these two fungi sheds a bright future of applying them to remediate lead‐contaminated environments.

The complete maternal mitochondrial genome sequence of Cuneopsis heudei (Bivalvia: Unionoida: Unionidae) - Qishuo Wang; Lu Ma; Lin Li; Ruijuan Feng; Huan Mu; Xin Wang; Cheng Wang; Xuepeng Wang (Conservation Genetics Resources, 2018)

Baseline sensitivity of Phytophthora capsici to the strobilurin fungicide benzothiostrobin and the efficacy of this fungicide - Dicheng Ma; Jiamei Zhu; Leiming He; Kaidi Cui; Wei Mu; Feng Liu (European Journal of Plant Pathology, 2018)

Identification and Field Evaluation of the Sex Pheromone of Orthaga achatina (Lepidoptera: Pyralidae) - Qi Yan; Hai-Dong Li; Yan Chen; Zhan-Feng Ye; Xi-Yu You; Jun Zhou; Lan-Fang Mu; Shi-Jing Liu; Xiang-Bo Kong; Sajjad Ali Khuhro; Shuang-Lin Dong (Journal of Chemical Ecology, 2018)

Hoeflea prorocentri sp. nov., isolated from a culture of the marine dinoflagellate Prorocentrum mexicanum PM01 - Qiao Yang; Zhi-Wei Jiang; Cheng-Hui Huang; Ruo-Nan Zhang; Ling-Zhi Li; Guang Yang; Li-Juan Feng; Guang-Feng Yang; Heng Zhang; Xiao-Ling Zhang; Jun Mu (Antonie van Leeuwenhoek, 2018)

Disruption of bacterial balance in the gut of Portunus trituberculatus induced by Vibrio alginolyticus infection - Mengjie Xia; Feng Pei; Changkao Mu; Yangfang Ye; Chunlin Wang (Journal of Oceanology and Limnology, 2018)

Favorable compatibility of nitenpyram with the aphid predator, Coccinella septempunctata L. (Coleoptera: Coccinellidae) - Jiangong Jiang; Dicheng Ma; Zhengqun Zhang; Caihong Yu; Feng Liu; Wei Mu (Environmental Science and Pollution Research, 2018)

Influence of vertical loads on lateral behaviour of monopiles in sand - Linlong Mu; Xingyu Kang; Kai Feng; Maosong Huang; Jie Cao (European Journal of Environmental and Civil Engineering, 2018)

Association of TRIMCyp and TRIM5α from assam macaques leads to a functional trade-off between HIV-1 and N-MLV inhibition - Dan Mu; Jia-Wu Zhu; Feng-Liang Liu; Hong-Yi Zheng; Yong-Tang Zheng (Science China Life Sciences, 2018)

Anaerobic biodegradation of partially hydrolyzed polyacrylamide in long-term methanogenic enrichment cultures from production water of oil reservoirs - Hao Hu; Jin-Feng Liu; Cai-Yun Li; Shi-Zhong Yang; Ji-Dong Gu; Bo-Zhong Mu (Biodegradation, 2018)

Correction to: Ponticoccus alexandrii sp. nov., a novel bacterium isolated from the marine toxigenic dinoflagellate Alexandrium minutum - Qiao Yang; Xiaoling Zhang; Lingzhi Li; Ruonan Zhang; Lijuan Feng; Jun Mu (Antonie van Leeuwenhoek, 2018)

Ponticoccus alexandrii sp. nov., a novel bacterium isolated from the marine toxigenic dinoflagellate Alexandrium minutum - Qiao Yang; Xiaoling Zhang; Lingzhi Li; Ruonan Zhang; Lijuan Feng; Jun Mu (Antonie van Leeuwenhoek, 2018)

Anomalous gray matter structural networks in recent onset post-traumatic stress disorder - Shun Qi; Yun-Feng Mu; Long-Biao Cui; Jian Zhang; Fan Guo; Qing-Rong Tan; Mei Shi; Kang Liu; Yi-Bin Xi; Nan-Yin Zhang; Xiao-Liang Zhang; Yong He; et al. (Brain Imaging and Behavior, 2018)

Assessment of the baseline sensitivity and resistance risk of Colletotrichum acutatum to fludioxonil - Yangyang Gao; Lifei He; Wei Mu; Beixing Li; Jin Lin; Feng Liu (European Journal of Plant Pathology, 2018)

Characterization of bacterial composition and diversity in a long-term petroleum contaminated soil and isolation of high-efficiency alkane-degrading strains using an improved medium - Jun Zheng; Jun-Qiao Feng; Lei Zhou; Serge Maurice Mbadinga; Ji-Dong Gu; Bo-Zhong Mu (World Journal of Microbiology and Biotechnology, 2018)

Underestimated effects of sediments on enhanced startup performance of biofilm systems for polluted source water pretreatment - Zheng-hui Lv; Jing Wang; Guang-feng Yang; Li-juan Feng; Jun Mu; Liang Zhu; Xiang-yang Xu (Biodegradation, 2018)

Characteristics of nitrogen removal and microbial community in biofilm system via combination of pretreated lignocellulosic carriers and various conventional fillers - Jing Zhao; Lijuan Feng; Jincheng Dai; Guangfeng Yang; Jun Mu (Biodegradation, 2017)

Sensitivity of Colletotrichum acutatum to six fungicides and reduction in incidence and severity of chili anthracnose using pyraclostrobin - Yang-Yang Gao; Li-Fei He; Bei-Xing Li; Wei Mu; Jin Lin; Feng Liu (Australasian Plant Pathology, 2017)

Propionate metabolism and diversity of relevant functional genes by in silico analysis and detection in subsurface petroleum reservoirs - Tao Yang; Serge Maurice Mbadinga; Lei Zhou; Shi-Zhong Yang; Jing-Feng Liu; Ji-Dong Gu; Bo-Zhong Mu (World Journal of Microbiology and Biotechnology, 2017)

Optimization of continuous-flow solid-phase denitrification via coupling carriers in enhancing simultaneous removal of nitrogen and organics for agricultural runoff purification - Yi Lu; Xiaoqing Zhang; Lijuan Feng; Guangfeng Yang; Zhou Zheng; Junzhi Liu; Jun Mu (Biodegradation, 2017)

Response of performance and bacterial community to oligotrophic stress in biofilm systems for raw water pretreatment - Li-juan Feng; Rong Jia; Jing-ya Sun; Jing Wang; Zheng-hui Lv; Jun Mu; Guang-feng Yang (Biodegradation, 2017)

The potential of fludioxonil for anthracnose control on China chili fruit - Yang-Yang Gao; Li-Fei He; Bei-Xing Li; Wei Mu; Jin Lin; Feng Liu (Phytoparasitica, 2017)

A new quinolinone and its natural/artificial derivatives from a shark gill-derived fungus Penicillium polonicum AP2T1 - Yi Zhang; Jun Mu; Frank Essmann; Yan Feng; Markus Kramer; Hai-yan Bao; Stephanie Grond (Natural Product Research, 2017)

Puerarin-7-O-glucuronide, a water-soluble puerarin metabolite, prevents angiotensin II-induced cardiomyocyte hypertrophy by reducing oxidative stress - Ning Hou; Bin Cai; Cai-Wen Ou; Zhen-Hui Zhang; Xia-Wen Liu; Mu Yuan; Gan-Jian Zhao; Shi-Ming Liu; Long-Gen Xiong; Jian-Dong Luo; Cheng-Feng Luo; Min-Sheng Chen (Naunyn-Schmiedeberg's Archives of Pharmacology, 2017)

Functional genes and thermophilic microorganisms responsible for arsenite oxidation from the shallow sediment of an untraversed hot spring outlet - Ye Yang; Yao Mu; Xian-Chun Zeng; Weiwei Wu; Jie Yuan; Yichen Liu; E. Guoji; Feng Luo; Xiaoming Chen; Hao Li; Jianing Wang (Ecotoxicology, 2017)

Geotechnical characteristics of weathered granitic gneiss with geo-hazards investigation of pit excavation in Guangzhou, China - Mu Chen; Shui-Long Shen; Huai-Na Wu; Zhi-Feng Wang; Suksun Horpibulsuk (Bulletin of Engineering Geology and the Environment, 2017)

Improving N management through intercropping alleviates the inhibitory effect of mineral N on nodulation in pea - Falong Hu; Cai Zhao; Fuxue Feng; Qiang Chai; Yanping Mu; Yan Zhang (Plant and Soil, 2017)

PDV2 has a dosage effect on chloroplast division in Arabidopsis - Ning Chang; Qingqing Sun; Yiqiong Li; Yajuan Mu; Jinglei Hu; Yue Feng; Xiaomin Liu; Hongbo Gao (Plant Cell Reports, 2017)

Erratum to: Diurnal and seasonal variation of the elevation gradient of air temperature in the northern flank of the western Qinling Mountain range, China - Guo-yi Wang; Ming-fei Zhao; Mu-yi Kang; Kai-xiong Xing; Yu-hang Wang; Feng Xue; Chen Chen (Journal of Mountain Science, 2017)

Morphological and molecular characterization of the second backcross progenies of Ogu-CMS Chinese kale and rapeseed - Hai-long Yu; Zhi-yuan Li; Li-mei Yang; Yu-mei Liu; Mu Zhuang; Lu-gang Zhang; Hong-hao Lv; Zhan-sheng Li; Feng-qing Han; Xiao-ping Liu; Zhi-yuan Fang; Yang-yong Zhang (Euphytica, 2017)

Estimating observing locations for advancing beyond the winter predictability barrier of Indian Ocean dipole event predictions - Rong Feng; Wansuo Duan; Mu Mu (Climate Dynamics, 2017)

Transcription response of three putative trehalase genes to hormonal stimulation in the Colorado potato beetle, Leptinotarsa decemlineata (Coleoptera: Chrysomelidae) - Ji-Feng Shi; Qiang-Kun Sun; Li-Li Mu; Wen-Chao Guo; Guo-Qing Li (Applied Entomology and Zoology, 2017)

Vertical zonation of soil fungal community structure in a Korean pine forest on Changbai Mountain, China - Yuan Ping; Dongxue Han; Ning Wang; Yanbo Hu; Liqiang Mu; Fujuan Feng (World Journal of Microbiology and Biotechnology, 2017)

Remote sensing Penman–Monteith model to estimate catchment evapotranspiration considering the vegetation diversity - Fawen Li; Runxiang Cao; Yong Zhao; Dongjing Mu; Changfeng Fu; Feng Ping (Theoretical and Applied Climatology, 2017)

Diurnal and seasonal variation of the elevation gradient of air temperature in the northern flank of the western Qinling Mountain range, China - Guo-yi Wang; Ming-fei Zhao; Mu-yi Kang; Kai-xiong Xing; Yu-hang Wang; Feng Xue; Chen Chen (Journal of Mountain Science, 2017)

Lipopolysaccharide suppresses human immunodeficiency virus 1 reverse transcription in macrophages - Feng-Liang Liu; Jia-Wu Zhu; Dan Mu; Yong-Tang Zheng (Archives of Virology, 2016)

Non-integrating lentiviral vectors based on the minimal S/MAR sequence retain transgene expression in dividing cells - Zhen Xu; Feng Chen; Lingling Zhang; Jing Lu; Peng Xu; Guang Liu; Xuemin Xie; Wenli Mu; Yajun Wang; Depei Liu (Science China Life Sciences, 2016)

Ecological effects of rice-duck integrated farming on soil fertility and weed and pest control - Qing Teng; Xue-Feng Hu; Chang Cheng; Zhiqing Luo; Fan Luo; Yong Xue; Yijun Jiang; Zhen Mu; Liming Liu; Minyong Yang (Journal of Soils and Sediments, 2016)

Baseline sensitivity and control efficacy of antibiosis fungicide tetramycin against Botrytis cinerea - Yingying Song; Leiming He; Lele Chen; Yupeng Ren; Hongbao Lu; Su Geng; Wei Mu; Feng Liu (European Journal of Plant Pathology, 2016)

Propofol Prevents Hippocampal Neuronal Loss and Memory Impairment in Cerebral Ischemia Injury Through Promoting PTEN Degradation - Xin Chen; Ye-Mu Du; Feng Xu; Dai Liu; Yuan-Lin Wang (Journal of Molecular Neuroscience, 2016)

Development of a novel allele-specific Rfo marker and creation of Ogura CMS fertility-restored interspecific hybrids in Brassica oleracea - Hai-long Yu; Zhi-yuan Fang; Yu-mei Liu; Li-mei Yang; Mu Zhuang; Hong-hao Lv; Zhan-sheng Li; Feng-qing Han; Xiao-ping Liu; Yang-yong Zhang (Theoretical and Applied Genetics, 2016)

Characterization of the prokaryotic diversity through a stratigraphic permafrost core profile from the Qinghai-Tibet Plateau - Weigang Hu; Qi Zhang; Tian Tian; Dingyao Li; Gang Cheng; Jing Mu; Qingbai Wu; Fujun Niu; Lizhe An; Huyuan Feng (Extremophiles, 2016)

Sublethal concentration of benzothiazole adversely affect development, reproduction and longevity of Bradysia odoriphaga (Diptera: Sciaridae) - Yunhe Zhao; Peng Zhang; Yongbiao Zhai; Chengyu Chen; Qiuhong Wang; Jingkun Han; Zhengqun Zhang; Feng Liu; Wei Mu (Phytoparasitica, 2016)

Association of Optic Radiation Integrity with Cortical Thickness in Children with Anisometropic Amblyopia - Shun Qi; Yun-Feng Mu; Long-Biao Cui; Rong Li; Mei Shi; Ying Liu; Jun-Qing Xu; Jian Zhang; Jian Yang; Hong Yin (Neuroscience Bulletin, 2016)

Baseline sensitivity and efficacy of the sterol biosynthesis inhibitor triflumizole against Botrytis cinerea - Yingying Song; Datong Xu; Hongbao Lu; Leiming He; Lele Chen; Junan Shao; Chunmei Xu; Wei Mu; Feng Liu (Australasian Plant Pathology, 2016)

Glucocorticoid Receptor β Acts as a Co-activator of T-Cell Factor 4 and Enhances Glioma Cell Proliferation - Qian Wang; Pei-Hua Lu; Zhi-Feng Shi; Yan-Juan Xu; Jie Xiang; Yan-Xia Wang; Ling-Xiao Deng; Ping Xie; Ying Yin; Bin Zhang; Hui-Jun Mu; Wei-Zhen Qiao; et al. (Molecular Neurobiology, 2015)

Characteristics of hopanoid hydrocarbons in ambient PM10 and motor vehicle emissions and coal ash in Taiyuan, China - Feng Han; Junji Cao; Lin Peng; Huiling Bai; Dongmei Hu; Ling Mu; Xiaofeng Liu (Environmental Geochemistry and Health, 2015)

Fluazinam Residue and Dissipation in Potato Tubers and Vines, and in Field Soil - Xiaoxiao Feng; Kai Wang; Zhaobin Mu; Yuzhen Zhao; Hongyan Zhang (American Journal of Potato Research, 2015)

Molecular cloning, characterization and evolutionary analysis of vitellogenin in Chinese giant salamander Andrias davidianus - Hai-feng Tian; Yan Meng; Qiao-mu Hu; Han-bing Xiao (Biologia, 2015)

Effects of metalloprotease anthrax lethal factor on its peptide-based inhibitor R9LF-1 - Qingsheng Kong; Yuezhang Song; Minlei Mu; Xiaolin Han; Chuanping Si; Feng Li (Molecular and Cellular Biochemistry, 2015)

Influence of positive and negative Indian Ocean Dipoles on ENSO via the Indonesian Throughflow: Results from sensitivity experiments - Qian Zhou; Wansuo Duan; Mu Mu; Rong Feng (Advances in Atmospheric Sciences, 2015)

Safety and efficacy study of lung cancer stem cell vaccine - Mao Lin; Shu-Ying Li; Ke-Cheng Xu; Zheng-Ping Liu; Feng Mu; Yuan-Ying Yuan; Xiao-Hua Wang; Ji-Bing Chen; Qiao Li (Immunologic Research, 2015)

Antibiotic resistance pattern and gene expression of non-typhoid Salmonella in riversheds - Chao-Yu Hsu; Bing-Mu Hsu; Wen-Tsai Ji; Jung-Sheng Chen; Tsui-Kang Hsu; Dar-Der Ji; Shao-Feng Tseng; Yi-Chou Chiu; Po-Min Kao; Yu-Li Huang (Environmental Science and Pollution Research, 2015)

Proteomics analysis for enhanced lipid accumulation in oleaginous Chlorella vulgaris under a heterotrophic-Na+ induction two-step regime - Yuqin Li; Jinxiu Mu; Di Chen; Hua Xu; Fangxin Han; Bo Feng; Hongyan Zeng (Biotechnology Letters, 2015)

Detection of inherited mutations for hereditary cancer using target enrichment and next generation sequencing - Yanfang Guan; Hong Hu; Yin Peng; Yuhua Gong; Yuting Yi; Libin Shao; Tengfei Liu; Gairui Li; Rongjiao Wang; Pingping Dai; Yves-Jean Bignon; Zhe Xiao; et al. (Familial Cancer, 2015)

Comparison of Bradysia odoriphaga Yang and Zhang reared on artificial diet and different host plants based on an age-stage, two-sex life table - Peng Zhang; Feng Liu; Wei Mu; Qiuhong Wang; Hui Li (Phytoparasitica, 2015)

A Potential Association Between Antibiotic Abuse and Existence of Related Resistance Genes in Different Aquatic Environments - Chao-Yu Hsu; Bing-Mu Hsu; Wen-Tsai Ji; Tien-Yu Chang; Po-Min Kao; Shao-Feng Tseng; Tsung-Yu Shen; Feng-Cheng Shih; Cheng-Wei Fan; Jorn-Hon Liu (Water, Air, & Soil Pollution, 2015)

Study on the “winter persistence barrier” of Indian Ocean dipole events using observation data and CMIP5 model outputs - Rong Feng; Mu Mu; Wansuo Duan (Theoretical and Applied Climatology, 2014)

Expression of bone morphogenetic protein 2, 4, and related components of the BMP signaling pathway in the mouse uterus during the estrous cycle - Yan Li; Quan-wei Wei; Jian-gang Feng; Mu-lin Xu; Rui-hua Huang; Fang-xiong Shi (Journal of Zhejiang University-SCIENCE B, 2014)

Inhibiting mast cell degranulation by HO-1 affects dendritic cell maturation in vitro - Yuan-yuan Ma; Mu-qing Yang; Chun-feng Wang; Jing Ding; Ji-yu Li (Inflammation Research, 2014)

Structural characterization of rhamnolipid produced by Pseudonomas aeruginosa strain FIN2 isolated from oil reservoir water - Jin-Feng Liu; Gang Wu; Shi-Zhong Yang; Bo-Zhong Mu (World Journal of Microbiology and Biotechnology, 2014)

Four chlorinated depsidones from a seaweed-derived strain of Aspergillus unguis and their new biological activities - Yi Zhang; Jun Mu; Yan Feng; Lixue Wen; Jinyuan Han (Natural Product Research, 2014)

Genetic variation at 8q24, family history of cancer, and upper gastrointestinal cancers in a Chinese population - Heather P. Tarleton; Shen-Chih Chang; Sungshim Lani Park; Lin Cai; Baoguo Ding; Na He; Shehnaz K. Hussain; Qingwu Jiang; Li-Na Mu; Jianyu Rao; Hua Wang; Nai-Chieh Y. You; et al. (Familial Cancer, 2014)

Cloning and expression analysis of Foxl2 during the reproductive cycle in Korean rockfish, Sebastes schlegeli - Wei J. Mu; Hai S. Wen; Ji F. Li; Feng He (Fish Physiology and Biochemistry, 2013)

A new bergenin derivative from the rhizome of Ardisia gigantifolia - Li-Hua Mu; Ju-Qiang Feng; Ping Liu (Natural Product Research, 2013)

The role of Akt/FoxO3a in the protective effect of venlafaxine against corticosterone-induced cell death in PC12 cells - Haitao Wang; Xuanhe Zhou; Jianchu Huang; Nan Mu; Zeli Guo; Qiang Wen; Rikang Wang; Shaorui Chen; Zhong-Ping Feng; Wenhua Zheng (Psychopharmacology, 2013)

Characterization of ribose-5-phosphate isomerase converting d-psicose to d-allose from Thermotoga lettingae TMO - Zaiping Feng; Wanmeng Mu; Bo Jiang (Biotechnology Letters, 2013)

Cloning and expression analysis of follicle-stimulating hormone and luteinizing hormone receptor during the reproductive cycle in Korean rockfish (Sebastes schlegeli) - Wei J. Mu; Hai S. Wen; Feng He; Ji F. Li; Miao Liu; Yuan Q. Zhang; Jian Hu; Bao X. Qi (Fish Physiology and Biochemistry, 2013)

Indoor air pollution and risk of lung cancer among Chinese female non-smokers - Lina Mu; Li Liu; Rungui Niu; Baoxing Zhao; Jianping Shi; Yanli Li; Mya Swanson; William Scheider; Jia Su; Shen-Chih Chang; Shunzhang Yu; Zuo-Feng Zhang (Cancer Causes & Control, 2013)

Cloning and expression analysis of vasa during the reproductive cycle of Korean rockfish, Sebastes schlegeli - Weijie Mu; Haishen Wen; Feng He; Jifang Li; Miao Liu; Ruiqin Ma; Yuanqing Zhang; Jian Hu; Baoxia Qi (Journal of Ocean University of China, 2013)

Complete nucleotide sequence of a Chinese isolate of Grapevine leafroll-associated virus 3 reveals a 5′ UTR of 802 nucleotides - Fei Fei; Mu-Di Lyu; Jie Li; Zai-Feng Fan; Yu-Qin Cheng (Virus Genes, 2013)

Erratum to: UDP-glucuronosyltransferase 1A1 is the principal enzyme responsible for puerarin metabolism in human liver microsomes - Cheng-Feng Luo; Bin Cai; Ning Hou; Mu Yuan; Shi-Ming Liu; Hong Ji; Long-Gen Xiong; Wei Xiong; Jian-Dong Luo; Min-Sheng Chen (Archives of Toxicology, 2012)

UDP-glucuronosyltransferase 1A1 is the principal enzyme responsible for puerarin metabolism in human liver microsomes - Cheng-Feng Luo; Bin Cai; Ning Hou; Mu Yuan; Shi-Ming Liu; Hong Ji; Long-Gen Xiong; Wei Xiong; Jian-Dong Luo; Min-Sheng Chen (Archives of Toxicology, 2012)

Occurrence of diarrheagenic Escherichia coli genes in raw water of water treatment plants - Shih-Wei Huang; Bing-Mu Hsu; Yen-Jui Su; Dar-Der Ji; Wei-Chen Lin; Jyh-Larng Chen; Feng-Cheng Shih; Po-Min Kao; Yi-Chou Chiu (Environmental Science and Pollution Research, 2012)

OsPFA-DSP1, a rice protein tyrosine phosphatase, negatively regulates drought stress responses in transgenic tobacco and rice plants - Bing Liu; Jieqiong Fan; Yang Zhang; Peiqiang Mu; Peng Wang; Jianbin Su; Huihuang Lai; Shaowu Li; Dongru Feng; Jinfa Wang; Hongbin Wang (Plant Cell Reports, 2012)

Imprinting analysis of porcine DIO3 gene in two fetal stages and association analysis with carcass and meat quality traits - Mu Qiao; Hua-Yu Wu; Ling Guo; Shu-Qi Mei; Peng-Peng Zhang; Feng-E Li; Rong Zheng; Chang-Yan Deng (Molecular Biology Reports, 2012)

Mutations in exons of the CYP17-II gene affect sex steroid concentration in male Japanese flounder (Paralichthys olivaceus) - Ruiqin Ma; Feng He; Haishen Wen; Jifang Li; Bao Shi; Dan Shi; Miao Liu; Weijie Mu; Yuanqing Zhang; Jian Hu; Weiguo Han; Jianan Zhang; et al. (Journal of Ocean University of China, 2012)

Expression patterns of cytochrome P450 aromatase genes during ovary development and their responses to temperature stress in female yellow catfish (Pelteobagrus fulvidraco) - Miao Liu; Haishen Wen; Feng He; Jifang Li; Dan Shi; Jian Hu; Yuanqing Zhang; Ruiqin Ma; Weijie Mu; Baoxia Qi (Journal of Ocean University of China, 2011)

Positive allelopathic stimulation and underlying molecular mechanism of achyranthe under continuous monoculture - Zhen-Fang Li; Zi-Guan Zhang; Dong-Feng Xie; Lin-Quan Dai; Lan-Fang Zhu; Ji Li; Zong-Quan Liu; Yan-Qiu Yang; Lin-Kun Wu; Mu-Ji Huang; Zhong-Yi Zhang; Wen-Xiong Lin (Acta Physiologiae Plantarum, 2011)

Resistance of Spodoptera exigua to ten insecticides in Shandong, China - Chao Zhou; Yongqiang Liu; Weili Yu; Zhaorong Deng; Ming Gao; Feng Liu; Wei Mu (Phytoparasitica, 2011)

Activation of GH signaling and GH-independent stimulation of growth in zebrafish by introduction of a constitutively activated GHR construct - A. S. Ishtiaq Ahmed; Feng Xiong; Shao-Chen Pang; Mu-Dan He; Michael J. Waters; Zuo-Yan Zhu; Yong-Hua Sun (Transgenic Research, 2011)

Genetic polymorphism analysis of 15 STR loci in Chinese Hui ethnic group residing in Qinghai province of China - Ya-jun Deng; Bo-feng Zhu; Chun-mei Shen; Hong-dan Wang; Jing-feng Huang; Yuan-zhe Li; Hai-xia Qin; Hao-fang Mu; Jie Su; Jie Wu; Bo Zhang; Shuan-liang Fan (Molecular Biology Reports, 2011)

Polyclonal rabbit anti-murine plasmacytoma cell globulins induce myeloma cells apoptosis and inhibit tumour growth in mice - Bo Mu; Jin-liang Yang; Lan-tu Gou; Yu-qin Yao; Yan Zhou; Zhi-hui Cheng; Hua-shan Shi; Zhi-yong Li; Yuan Wen; Fei Leng; Feng-yu Cui; Tian-tai Ma; et al. (Apoptosis, 2011)

Development and characterization of a mouse floxed Bmp2 osteoblast cell line that retains osteoblast genotype and phenotype - Li-an Wu; Junsheng Feng; Lynn Wang; Yan-dong Mu; Andrew Baker; Kevin J. Donly; Stephen E. Harris; Mary MacDougall; Shuo Chen (Cell and Tissue Research, 2011)

Microarray analysis of the gene expression profile in the midgut of silkworm infected with cytoplasmic polyhedrosis virus - Ping Wu; Xiu Wang; Guang-xing Qin; Ting Liu; Yun-Feng Jiang; Mu-Wang Li; Xi-Jie Guo (Molecular Biology Reports, 2011)

Ovate family protein 1 as a plant Ku70 interacting protein involving in DNA double-strand break repair - Yung-Kai Wang; Wen-Chi Chang; Pei-Feng Liu; Mu-Kai Hsiao; Chueh-Tsun Lin; Shih-Ming Lin; Rong-Long Pan (Plant Molecular Biology, 2010)

Indole Affects Biofilm Formation in Bacteria - Mingxi Hu; Can Zhang; Yufei Mu; Qianwei Shen; Yongjun Feng (Indian Journal of Microbiology, 2010)

Immune response to fused core protein of hepatitis C virus and truncated tetanus toxin peptides in mice - Xing-bin Hu; Qiao-hong Yue; Hai-feng Ouyang; Yao-zhen Chen; Xue-qing Xu; Wen Yin; San-hua Wei; Xian-qing Zhang; Shi-jie Mu (Archives of Virology, 2010)

Molecular characterization, expression profile and association analysis with carcass traits of porcine LCAT gene - Mu Qiao; Hua-Yu Wu; Feng-E Li; Si-Wen Jiang; Yuan-Zhu Xiong; Chang-Yan Deng (Molecular Biology Reports, 2010)

Effect of high glucose concentration on VEGF and PEDF expression in cultured retinal Müller cells - Hua Mu; Xiao-Mei Zhang; Jian-Ju Liu; Li Dong; Zhuo-Lei Feng (Molecular Biology Reports, 2009)

Polymorphisms within promoter of Japanese flounder (Paralichthys olivaceus) ovary cytochrome P450-c19 (CYP19a) gene associated with reproductive traits - Feng He; Hai Shen Wen; Shuang Lin Dong; Bao Shi; Cai Fang Chen; Lian Shun Wang; Jun Yao; Xing Jiang Mu; Yu Guo Zhou (Fish Physiology and Biochemistry, 2009)

Interaction between aluminum toxicity and manganese toxicity in soybean (Glycine max) - Zhong Bao Yang; Jiang Feng You; Mu Yun Xu; Zhen Ming Yang (Plant and Soil, 2009)

Alu tandem sequences inhibit GFP gene expression by triggering chromatin wrapping - Xiu-Fang Wang; Xiaoyan Wang; Jing Liu; Jingjing Feng; Wenli Mu; Xiaojuan Shi; QinQing Yang; Xiaocui Duan; Ying Xie; Zhanjun Lu (Genes & Genomics, 2009)

Mapping QTLs of root morphological traits at different growth stages in rice - Yanying Qu; Ping Mu; Hongliang Zhang; Charles Y. Chen; Yongming Gao; Yuxiu Tian; Feng Wen; Zichao Li (Genetica, 2008)

Plants interactions between Suaeda salsa individuals are mediated by salinity stress - Hao Zhang; Jian-Na Li; Gen-Xuan Wang; Xin-Feng Dai; Mu-Qing Qiu; Ke-Feng Zheng (Acta Physiologiae Plantarum, 2007)

A collection of 10,096 indica rice full-length cDNAs reveals highly expressed sequence divergence between Oryza sativa indica and japonica subspecies - Xiaohui Liu; Tingting Lu; Shuliang Yu; Ying Li; Yuchen Huang; Tao Huang; Lei Zhang; Jingjie Zhu; Qiang Zhao; Danlin Fan; Jie Mu; Yingying Shangguan; et al. (Plant Molecular Biology, 2007)

Methylenetetrahydrofolate reductase (MTHFR) C677T and A1298C polymorphisms and the risk of primary Hepatocellular Carcinoma (HCC) in a Chinese population - Li-Na Mu; Wei Cao; Zuo-Feng Zhang; Lin Cai; Qing-Wu Jiang; Nai-Chieh You; Binh Yang Goldstein; Guo-Rong Wei; Chuan-Wei Chen; Qing-Yi Lu; Xue-Fu Zhou; Bao-Guo Ding; et al. (Cancer Causes & Control, 2007)

Earliest Triassic microbialites in the South China block and other areas: controls on their growth and distribution - Steve Kershaw; Yue Li; Sylvie Crasquin-Soleau; Qinglai Feng; Xinan Mu; Pierre-Yves Collin; Alan Reynolds; Li Guo (Facies, 2007)

Isolation and characterization of a novel thermophilic Bacillus strain degrading long-chain n-alkanes - Lei Wang; Yun Tang; Shuo Wang; Ru-Lin Liu; Mu-Zhi Liu; Yan Zhang; Feng-Lai Liang; Lu Feng (Extremophiles, 2006)

Using the Flow Cytometry to Quantify the Giardia Cysts and Cryptosporidium Oocysts in Water Samples - Bing-Mu Hsu; Nan-Min Wu; Hung-Der Jang; Feng-Cheng Shih; Min-Tao Wan; Chien-Min Kung (Environmental Monitoring and Assessment, 2005)

The role of earthworms (Eisenia fetida) in influencing bioavailability of heavy metals in soils - Bei Wen; Xiao-yu Hu; Ying Liu; Wei-sheng Wang; Mu-hua Feng; Xiao-quan Shan (Biology and Fertility of Soils, 2004)

PLGA/TPGS Nanoparticles for Controlled Release of Paclitaxel: Effects of the Emulsifier and Drug Loading Ratio - Li Mu; Si-Shen Feng (Pharmaceutical Research, 2003)